Optical laminate
Patent Information
- Application Number
- JP2022038107
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-05
- Filing Date
- 2022-03-11
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing organic electroluminescence (EL) display devices with circularly polarizing plates experience coloration of black images when viewed from oblique directions due to deviations in retardation values and phase differences from metal electrodes, requiring complex adjustments of polymerizable liquid crystal compounds and dichroic dyes to control retardation and coloring.
An optical laminate comprising a dye-containing layer, a polarizing layer, and a retardation layer, with the dye-containing layer positioned closer to the viewing side, allowing independent control of retardation value and coloring through specific absorbance ratios and orientations of dichroic dyes, compensating for deviations in retardation values and absorbing oblique reflections.
The optical laminate effectively reduces coloration of black images when viewed from oblique directions by independently controlling retardation and coloring, maintaining high image quality and visibility without inhibiting front light emission.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to an optical laminate, and more particularly to a display device equipped therewith. [Background technology]
[0002] In organic electroluminescent (hereinafter sometimes referred to as "organic EL") display devices, the panel that displays an image reflects light incident from the outside due to electrodes and other components incorporated inside. This reflected light makes it difficult to see the image displayed on the panel. For this reason, it is common practice to place a circular polarizer on the viewing side of the panel. A circular polarizer is an optical element made by stacking a linear polarizer and a λ / 4 phase difference plate, with the absorption axis of the linear polarizer and the slow axis of the λ / 4 phase difference plate forming an angle of approximately 45°. Typically, this circular polarizer is arranged so that the linear polarizer is on the viewing side and the λ / 4 phase difference plate is on the panel side. When an organic EL display device equipped with such a circular polarizer is viewed from the front, the effect of reflected light is reduced, making it possible to display black images with high image quality.
[0003] On the other hand, when an organic EL display device equipped with a circular polarizer is viewed from an oblique angle, the black image may appear colored. This is because, when an organic EL display device is viewed from an oblique angle, the λ / 4 phase difference plate functions outside of its ideal phase difference value. Furthermore, because metal electrodes are incorporated inside the panel of the organic EL display device, when viewed from an oblique angle, the image is affected by the phase difference of the reflected light reflected obliquely from the surface of the metal electrodes. Therefore, the black image when an organic EL display device is viewed from an oblique angle will be colored differently depending on the panel being viewed.
[0004] One solution that can solve these problems is the vertically aligned liquid crystal cured film disclosed in Patent Document 1. This vertically aligned liquid crystal cured film is a cured film obtained by curing a composition containing a dichroic dye and a polymerizable liquid crystal compound, with the polymerizable liquid crystal compound oriented vertically. Because this cured film exhibits a phase difference in the thickness direction, it functions as a so-called positive C phase difference plate. By combining this positive C phase difference plate and a λ / 4 phase difference plate and applying them to an organic EL display device, the phase difference value of the λ / 4 phase difference plate when viewed from an oblique direction is compensated, and the ideal phase difference value of the λ / 4 phase difference plate can be achieved.
[0005] In organic EL display devices using vertically aligned liquid crystal cured films, a slight tint may remain in the black image. The vertically aligned liquid crystal cured film described in Patent Document 1 also functions as a coloring layer due to the vertically aligned dichroic dyes within the film. Therefore, by selecting a dichroic dye in the vertically aligned liquid crystal film that is complementary to the coloring of the black image when the organic EL display device is viewed from an oblique angle, it is possible to eliminate the slight tint remaining in the black image. [Prior art documents] [Patent Documents]
[0006] [Patent Document 1] Japanese Patent Publication No. 2020-76920 [Overview of the project] [Problems that the invention aims to solve]
[0007] However, in linear polarizers, λ / 4 phase difference plates, and circular polarizers with laminated vertically aligned liquid crystal cured films, it is necessary to simultaneously control the phase difference value in the thickness direction of the vertically aligned liquid crystal cured film and the degree of coloration. This control requires the selection of polymerizable liquid crystal compounds for fabricating the vertically aligned liquid crystal cured film, the dichroic dyes to be combined with them, and adjustments to their mixing ratios, but these adjustments are complicated and require a lot of trial and error.
[0008] The inventors diligently studied how to easily manufacture a circular polarizing plate suitable for a target panel without requiring much trial and error. As a result, they discovered that two functions of a vertically aligned liquid crystal cured film—namely, the function as a positive C phase difference plate and the function as a colored layer equipped with vertically aligned dichroic dyes—are each performed by separate layers, and that by positioning the layer responsible for the colored layer function further towards the viewing side than the linear polarizing plate, the phase difference value in the thickness direction and the degree of coloring of the black image can be controlled independently of each other, leading to the present invention.
[0009] The present invention aims to provide an optical laminate and a display device equipped therewith that can easily reduce the coloration of black images when the display device is viewed from an oblique direction. [Means for solving the problem]
[0010] The present invention provides the following optical laminates and display devices. [1] An optical laminate comprising a dye-containing layer, a polarizing layer, and a phase difference layer having an in-plane phase difference in this order, The aforementioned dye-containing layer is It contains a dichroic dye that has maximum absorption in the wavelength range of 400 nm to 750 nm. An optical laminate that satisfies the relationship between equation (1) and equation (2) below. 0.001 ≤ A x C ≤ 0.3 (1) AxC(z=60) / AxC>2 (2) [In equations (1) and (2), AxC represents the absorbance of the dye-containing layer at the wavelength of maximum absorption in the range of 400 nm to 750 nm, and represents the absorbance of linearly polarized light oscillating in the x-axis direction. AxC(z=60) is the absorbance of the dye-containing layer at the wavelength of maximum absorption in the range of 400 nm to 750 nm, and represents the absorbance of linearly polarized light vibrating in the x-axis direction when the dye-containing layer is rotated 60° with the y-axis as the axis of rotation. The x-axis represents any direction within the plane of the dye-containing layer, and the y-axis represents a direction perpendicular to the x-axis within the plane of the dye-containing layer. [2] The optical laminate according to [1], which is a manufacturing intermediate for a laminate comprising, in this order, the dye-containing layer, the polarizing layer, the phase difference layer, and a vertically oriented liquid crystal layer cured in a state in which the polymerizable liquid crystal compound is oriented in the stacking direction of the optical laminate. [3] An optical laminate comprising, in this order, a dye-containing layer, a polarizing layer, a phase difference layer having an in-plane phase difference, and a vertically aligned liquid crystal layer, The vertically aligned liquid crystal layer is a cured layer in which polymerizable liquid crystal compounds are oriented in the stacking direction of the optical laminate. The aforementioned dye-containing layer is It contains a dichroic dye that has maximum absorption between wavelengths of 400 nm and 750 nm. An optical laminate that satisfies the relationship between equation (1) and equation (2) below. 0.001 ≤ A x C ≤ 0.3 (1) AxC(z=60) / AxC>2 (2) [In equations (1) and (2), AxC represents the absorbance of the dye-containing layer at the wavelength of maximum absorption in the range of 400 nm to 750 nm, and represents the absorbance of linearly polarized light oscillating in the x-axis direction. AxC(z=60) is the absorbance of the dye-containing layer at the wavelength of maximum absorption in the range of 400 nm to 750 nm, and represents the absorbance of linearly polarized light vibrating in the x-axis direction when the dye-containing layer is rotated 60° with the y-axis as the axis of rotation. The x-axis represents any direction within the plane of the dye-containing layer, and the y-axis represents a direction perpendicular to the x-axis within the plane of the dye-containing layer. [4] The optical laminate according to any one of [1] to [3], wherein the dye-containing layer further includes a cured product in which the polymerizable liquid crystal compound is oriented in the stacking direction of the optical laminate. [5] The optical laminate according to any one of [1] to [4], wherein the phase difference layer is a horizontally oriented liquid crystal layer that has been cured with polymerizable liquid crystal compounds oriented in a direction perpendicular to the stacking direction of the optical laminate. [6] The phase difference layer is an optical laminate according to any of [1] to [5] that satisfies the relationship in equation (3) below. ReA(450) / ReA(550)<1.00 (3) [In equation (3), ReA(450) and ReA(550) represent the in-plane phase difference values of the phase difference layer at wavelengths of 450 nm and 550 nm, respectively.] [7] The phase difference layer is an optical laminate according to any of [1] to [6] that satisfies the relationship in formula (4) below. 120nm ≤ ReA(550) ≤ 170nm (4) [In equation (4), ReA(550) represents the in-plane phase difference value of the phase difference layer at a wavelength of 550 nm.] [8] The optical laminate according to any one of [1] to [7], wherein the angle between the absorption axis of the polarizing layer and the slow phase axis of the phase difference layer is within the range of 45° ± 5°. [9] The optical laminate according to any one of [1] to [8], wherein the dichroic dye is an azo dye.
[10] The dye-containing layer is an optical laminate according to any of [1] to [9], satisfying any of the following [a1] to [a3]. [a1] Having maximum absorption in both the wavelength range of 400 nm to less than 550 nm and the wavelength range of 550 nm to less than 700 nm. [a2] Having maximum absorption in the wavelength range of 400 nm to less than 550 nm, and not having maximum absorption in the wavelength range of 550 nm to 700 nm. [a3] It does not have a maximum absorption in the wavelength range of 400 nm to less than 550 nm, but has a maximum absorption in the wavelength range of 550 nm to 700 nm.
[11] The optical laminate according to any one of [1] to
[10] , further comprising a hard coat layer on the side of the dye-containing layer opposite to the polarizing layer side.
[12] The optical laminate according to any one of [1] to
[11] , further comprising a protective film on the side of the dye-containing layer opposite to the polarizing layer side.
[13] Furthermore, an adhesive layer is provided between the phase difference layer and the vertically aligned liquid crystal layer, The optical laminate according to any one of [1] to
[12] , wherein the adhesive layer is in direct contact with the phase difference layer and the vertically aligned liquid crystal layer.
[14] The optical laminate according to
[13] , wherein the adhesive layer is a cured product layer of an ultraviolet-curable adhesive composition.
[15] comprising an optical laminate as described in any of [1] to
[14] , The optical laminate is a display device in which the dye-containing layer is positioned on the viewing side of the polarizing layer.
[16] The display device described in
[15] , which is an organic EL display device. [Effects of the Invention]
[0011] According to the optical laminate of the present invention, the coloration of black images when the display device is viewed from an oblique direction can be easily reduced. [Brief explanation of the drawing]
[0012] [Figure 1] This is a schematic cross-sectional view showing an optical laminate according to one embodiment of the present invention. [Figure 2] Figure 1 is a schematic diagram illustrating an example of a method for manufacturing an optical laminate. [Figure 3] This is a schematic cross-sectional view showing an optical laminate according to another embodiment of the present invention. [Figure 4] This is a schematic cross-sectional view showing an optical laminate according to yet another embodiment of the present invention. [Figure 5] This is a schematic cross-sectional view showing an optical laminate according to yet another embodiment of the present invention. [Modes for carrying out the invention]
[0013] Preferred embodiments of the optical laminate and display device will be described below with reference to the drawings. In each drawing, the same reference numerals are used for the same components as those described earlier, and their descriptions are omitted.
[0014] [Embodiment 1] (optical laminate) Figure 1 is a schematic cross-sectional view showing an optical laminate according to one embodiment of the present invention. As shown in Figure 1, the optical laminate 1 comprises a dye-containing layer 11, a polarizing layer 12, and a phase difference layer 13 having an in-plane phase difference in this order. Preferably, the optical laminate 1 constitutes an elliptical polarizer (including cases where it is a circular polarizer) with the polarizing layer 12 and the phase difference layer 13. The optical laminate 1 may further have a hard coat layer 16 or a protective film 15 on the side of the dye-containing layer 11 opposite to the polarizing layer 12. The optical laminate 1 shown in Figure 1 has both a hard coat layer 16 and a protective film 15. When the optical laminate 1 has both a hard coat layer 16 and a protective film 15, it is preferable to have the protective film 15 and the hard coat layer 16 in this order from the dye-containing layer 11 side.
[0015] It is preferable that each layer constituting the optical laminate 1 is laminated via a bonding layer, which is an adhesive layer or a bonding agent layer. When the optical laminate 1 has both a hard coat layer 16 and a protective film 15, it is preferable that the protective film 15 and the hard coat layer 16 are in direct contact without a bonding layer in between.
[0016] When the dye-containing layer 11, the polarizing layer 12, and the phase difference layer 13 are layers formed using liquid crystal compounds such as polymerizable liquid crystal compounds, the optical laminate 1 may have an alignment film for restricting the orientation of the liquid crystal compounds so as to be in direct contact with the layers formed using the liquid crystal compounds, or it may have a substrate for forming the layers or alignment film formed using the liquid crystal compounds. The layers or alignment film formed using the liquid crystal compounds and the substrate can be provided in direct contact with each other.
[0017] In the optical laminate 1, the angle between the absorption axis of the polarizing layer 12 and the slow phase axis of the phase difference layer 13 is preferably within the range of 45°±5°. The above angle may be within the range of 45°±3° or may be 45°.
[0018] The optical laminate 1 can also be used as a manufacturing intermediate for a laminate, as shown in Figure 3 below, to include, in this order, a dye-containing layer 11, a polarizing layer 12, a phase difference layer 13 having an in-plane phase difference, and a vertically aligned liquid crystal layer 17 (Figure 3) in which a polymerizable liquid crystal compound is cured with the polymerizable liquid crystal compound oriented in the stacking direction of the optical laminate 1. In this case, the above-mentioned laminate can be manufactured by providing the vertically aligned liquid crystal layer 17 on the phase difference layer 13 side of the optical laminate 1.
[0019] The optical laminate 1 can be used in a display device, and is particularly suitable for use in an organic EL display device. In the display device, the optical laminate 1 is arranged such that the dye-containing layer 11 is on the viewing side of the polarizing layer 12. The optical laminate 1 includes a dye-containing layer 11 that satisfies the relationships of equations (1) and (2) described later. Therefore, in a display device in which the optical laminate 1 is incorporated in the above arrangement, the dye-containing layer 11 can cancel out the coloration of the black image when the black image displayed on the panel is viewed from an oblique direction. This reduces the coloration of the black image when the display device is viewed from an oblique direction.
[0020] (Dye-containing layer) The dye-containing layer 11 contains a dichroic dye having maximum absorption in the wavelength range of 400 nm to 750 nm, and satisfies the relationship between the following formulas (1) and (2). 0.001 ≤ A x C ≤ 0.3 (1) AxC(z=60) / AxC>2 (2) [In formula (1) and formula (2), AxC represents the absorbance of the dye-containing layer 11 at the wavelength of maximum absorption in the range of 400 nm to 750 nm, and represents the absorbance of linearly polarized light oscillating in the x-axis direction. AxC(z=60) is the absorbance of the dye-containing layer 11 at the wavelength of maximum absorption in the range of 400 nm to 750 nm, and represents the absorbance of linearly polarized light vibrating in the x-axis direction when the dye-containing layer 11 is rotated 60° around the y-axis as the axis of rotation. The x-axis represents any direction within the plane of the dye-containing layer 11, and the y-axis represents the direction perpendicular to the x-axis within the plane of the dye-containing layer 11.
[0021] In this specification, all absorbances represent absorbance measured after removing the effect of interfacial reflection during measurement. Methods for removing the effect of interfacial reflection include, for example, using a spectrophotometer to set the absorbance at wavelengths where the absorption of the compound is negligible in the long-wavelength region, such as 800 nm, to 0, and then measuring the absorbance at wavelengths in the region where the absorption of the compound exists.
[0022] The dye-containing layer 11 contains at least one dichroic dye (hereinafter sometimes referred to as "this dichroic dye") having maximum absorption in the wavelength range of 400 nm to 750 nm. A dichroic dye is a dye in which the absorbance along the long axis of the molecule and the absorbance along the short axis are different. Since the dye-containing layer 11 satisfies the relationship of formulas (1) and (2) above, it is considered that this dichroic dye is oriented in the dye-containing layer 11 in the stacking direction of the optical laminate 1. The dye-containing layer 11 may also contain dichroic dyes other than this dichroic dye.
[0023] When viewing an OLED display panel equipped with a circular polarizer from an oblique angle, the black image may appear colored. This is because the phase difference layer contained in the circular polarizer functions outside of the ideal phase difference value. Furthermore, since metal electrodes are incorporated inside the OLED display panel, viewing the OLED display from an oblique angle is affected by the phase difference of the reflected light reflected obliquely from the surface of the metal electrodes. Therefore, the black image when viewing an OLED display from an oblique angle will be colored differently depending on the panel being viewed.
[0024] The optical laminate 1 of this embodiment includes a dye-containing layer 11 containing a dichroic dye that has light absorption capabilities capable of canceling out the coloration of the panel when displaying black when the display device is viewed from an oblique direction. Therefore, in a display device incorporating the optical laminate 1, the hue difference between the front reflection hue and the oblique reflection hue when displaying black can be reduced. For example, the maximum absorption wavelength of the dye-containing layer 11 in the 400-750 nm range is adjusted so that the reflection hue of the dye-containing layer 11 when viewed from the same direction as the hue when the panel is viewed from a 45° oblique direction when displaying black is complementary to the hue of the panel. This makes it possible to cancel out the coloration when the display device equipped with the optical laminate 1 is viewed from a 45° oblique direction. Therefore, the oblique reflection hue can be improved without affecting the front reflection hue when the display device is displaying black, and the hue difference between the front reflection hue and the oblique reflection hue can be suppressed, thereby reducing the coloration of the black image when the display device is viewed from an oblique direction.
[0025] In equations (1) and (2) above, AxC can be measured by incident linearly polarized light vibrating in the x-axis direction toward the surface of the dye-containing layer 11 from the thickness direction of the dye-containing layer 11 (hereinafter sometimes referred to as the "z-axis direction"). Equation (1) above means that the absorbance in the front direction of the dye-containing layer 11 (the direction perpendicular to the surface of the dye-containing layer 11, and the stacking direction of the optical laminate 1) is 0.001 or more and 0.3 or less. The smaller the value of AxC, the more accurately the dichroic dye is oriented toward the stacking direction of the optical laminate 1 relative to the surface of the dye-containing layer 11. If AxC exceeds 0.3, the coloring in the front direction of the dye-containing layer 11 becomes stronger, which, in combination with the phase difference layer 13, inhibits the emission of light from the front of the display device. Therefore, AxC is preferably 0.1 or less, and more preferably 0.05 or less. The lower limit of AxC is usually 0.001 or more, preferably 0.003 or more, and even more preferably 0.005 or more.
[0026] In equation (2) above, AxC(z=60) can be measured by rotating the dye-containing layer 11 by 60° around the y-axis as the axis of rotation, and then incident the same linearly polarized light as the linearly polarized light used to measure AxC. Here, the rotation of the dye-containing layer 11 is performed by rotating the dye-containing layer 11, which is in the state in which AxC was measured, by 60° around the y-axis as the axis of rotation in the direction of incidence of the linearly polarized light. If AxC(z=60) / AxC is 2 or less, it becomes difficult to obtain good light absorption anisotropy, and in particular, it may hinder the emission of light from the front of the display device. AxC(z=60) / AxC is preferably 2.5 or more, and more preferably 3 or more. On the other hand, if AxC(z=60) / AxC is too large, it may hinder the emission of light, especially when the display device is viewed from an oblique direction, so AxC(z=60) / AxC is preferably 50 or less, more preferably 30 or less, and even more preferably 20 or less. Furthermore, AxC(z=60) is preferably 0.01 or greater, more preferably 0.05 or greater, even more preferably 0.10 or greater, also preferably 1.0 or less, more preferably 0.5 or less, and even more preferably 0.3 or less.
[0027] In this specification, in the dye-containing layer 11, the absorbance AyC of linearly polarized light vibrating in the y-axis direction is usually approximately equal to AxC. If AxC and AyC are different, dichroism will occur in the plane, which may particularly hinder light emission from the front of the display device.
[0028] If the dye-containing layer 11 satisfies the above formulas (1) and (2), it can be said that the dye-containing layer 11 has excellent polarization performance (absorption anisotropy), thereby effectively transmitting light from the front and effectively absorbing light from oblique directions. Therefore, in a display device incorporating the optical laminate 1 including the dye-containing layer 11, the hue difference between the front-reflected hue and the oblique-reflected hue in black display can be suppressed without hindering the front-emitting light of the display device.
[0029] The AxC and AxC(z=60) of the dye-containing layer 11 can be controlled, for example, by adjusting the thickness of the dye-containing layer 11, the conditions of the manufacturing process, the type and / or amount of the dichroic dye contained in the dye-containing layer 11, etc. As described later, if the dye-containing layer 11 contains a cured product in which the polymerizable liquid crystal compound is oriented in the stacking direction of the optical laminate 1, AxC and AxC(z=60) can also be controlled by adjusting the type and / or amount of the polymerizable liquid crystal compound, and can be controlled by the host-guest interaction between the cured product (liquid crystal) and the dichroic dye. The value of AxC(z=60) / AxC is approximately 2 to 10 when the polymerizable liquid crystal compound is a nematic liquid crystal, and approximately 5 to 30 when it is a smectic liquid crystal, and can be appropriately selected according to the desired optical properties.
[0030] As described above, in a display device in which the optical laminate 1 is incorporated such that the dye-containing layer 11 is on the visible side of the polarizing layer 12, the dye-containing layer 11 can be used to suppress the hue difference between the front-reflected hue and the oblique-reflected hue in black display. Because the dye-containing layer 11 is positioned on the visible side of the polarizing layer 12 in the display device, even if the dye-containing layer 11 has a phase difference in the thickness direction, it is not perceived by the human eye. Therefore, the dye-containing layer 11 may have a phase difference in the thickness direction, and the magnitude of this value is not particularly limited. Thus, the thickness of the dye-containing layer 11 and the density of the dichroic dye can be adjusted to satisfy equations (1) and (2) without being constrained by the phase difference value in the thickness direction of the dye-containing layer 11. In this way, by using the optical laminate 1, the hue difference between the front-reflected hue and the oblique-reflected hue in black display can be easily suppressed.
[0031] When the phase difference layer 13 functions outside the ideal phase difference value, the resulting color can vary, but it often changes to red or blue, for example. For this reason, in a display device combining a panel and an optical laminate 1, it is preferable that the dye-containing layer 11 satisfies any of the following conditions [a1] to [a3] in order to easily adjust the oblique reflection hue when observed from an oblique direction to a desired hue. [a1] Having maximum absorption in both the wavelength range of 400 nm to less than 550 nm and the wavelength range of 550 nm to less than 700 nm. [a2] Having maximum absorption in the wavelength range of 400 nm to less than 550 nm, and not having maximum absorption in the wavelength range of 550 nm to 700 nm. [a3] It does not have a maximum absorption in the wavelength range of 400 nm to less than 550 nm, but has a maximum absorption in the wavelength range of 550 nm to 700 nm.
[0032] When the dye-containing layer 11 satisfies [a3] above, it can absorb reflected light leaking from an oblique direction. However, from the viewpoint of visibility when the display device is illuminated, it is preferable to use a dye-containing layer 11 that satisfies [a1] or [a2] above. When the dye-containing layer 11 satisfies [a2] above, the oblique reflection hue when the display device is displayed in black can be improved by using the dye-containing layer 11 in combination with an elliptical polarizer that exhibits significant reflection of light in the wavelength range of 400 nm to less than 550 nm when displaying black at an oblique angle of 45°. Furthermore, when the dye-containing layer 11 satisfies [a3] above, the oblique reflection hue when the display device is displayed in black can be improved by using the dye-containing layer 11 in combination with an elliptical polarizer that exhibits significant reflection of light in the wavelength range of 550 nm to 700 nm when displaying black at an oblique angle of 45°.
[0033] The dye-containing layer 11 preferably contains a cured product in which the polymerizable liquid crystal compound is oriented in the stacking direction of the optical laminate 1. Including this cured product makes it easier to orient the dichroic dye in the stacking direction of the optical laminate 1 within the cured film formed by the cured product, thus facilitating the fabrication of the dye-containing layer 11. Details of the dichroic dye and polymerizable liquid crystal compound will be described later.
[0034] The thickness of the dye-containing layer 11 is not particularly limited and can be appropriately selected depending on the structure of the display device, etc. The thickness of the dye-containing layer 11 is preferably 0.1 μm or more, more preferably 0.2 μm or more, preferably 10 μm or less, more preferably 3 μm or less, and even more preferably 2 μm or less.
[0035] (Polarizing layer) The polarizing layer 12 is a linearly polarized layer that transmits linearly polarized light having a vibration plane perpendicular to the absorption axis when unpolarized light is incident on it. Examples of the polarizing layer 12 include a stretched film on which a dye having absorption anisotropy is adsorbed, and a film containing a polarizing layer formed by coating a base film with a composition containing a dye having absorption anisotropy. Details of the polarizing layer 12 will be described later.
[0036] (phase contrast layer) The phase difference layer 13 has an in-plane phase difference. The value of the in-plane phase difference of the phase difference layer 13 is not particularly limited, but it is preferable that the in-plane phase difference value ReA(550) of the phase difference layer 13 at a wavelength of 550 nm is 50 nm or more, and more preferably 90 nm or more. The ReA(550) of the phase difference layer 13 is more preferably in the range of 100 nm to 250 nm, and particularly preferably in the range of the following formula (4). 120nm ≤ ReA(550) ≤ 170nm (4) [In equation (4), ReA(550) represents the in-plane phase difference value of the phase difference layer 13 at a wavelength of 550 nm.]
[0037] When the in-plane phase difference ReA(550) of the phase difference layer 13 is within the range of formula (4) above, the effect of improving the front reflection hue when displaying black in the display device incorporating the optical laminate 1 (effect of suppressing coloration) becomes significant. The in-plane phase difference value ReA(550) is more preferably 130 nm or more, and more preferably 150 nm or less.
[0038] The phase difference layer 13 may be, for example, a stretched film having an in-plane phase difference, or it may be a cured layer in which a polymerizable liquid crystal compound is oriented in a direction perpendicular to the stacking direction of the optical laminate 1 (hereinafter sometimes referred to as the "horizontal direction") (hereinafter sometimes referred to as the "horizontal oriented liquid crystal layer"). The phase difference layer 13 is preferably a horizontal oriented liquid crystal layer because it is possible to easily control the in-plane phase difference value of the phase difference layer 13 to a desired value and it can be made into a thin film.
[0039] The phase difference layer 13 preferably satisfies the relationship shown in equation (3) below. ReA(450) / ReA(550)<1.00 (3) [In equation (3), ReA(450) and ReA(550) represent the in-plane phase difference values of the phase difference layer 13 at wavelengths of 450 nm and 550 nm, respectively.]
[0040] Here, the in-plane phase difference value ReA(λ) of the phase difference layer 13 at wavelength λ is expressed by the following equation (6). ReA(λ)=(nxA(λ)-nyA(λ))×dA (6) [In formula (6), nxA(λ) represents the principal refractive index at wavelength λnm in the plane of the phase difference layer 13. nyA(λ) represents the refractive index at wavelength λnm in a direction perpendicular to the direction of nxA(λ) within the same plane as nxA(λ). dA indicates the thickness of the phase difference layer 13.
[0041] When the phase difference layer 13 satisfies the relationship in equation (3) above, the phase difference layer 13 exhibits so-called inverse wavelength dispersion, where the in-plane phase difference value at short wavelengths is smaller than the in-plane phase difference value at long wavelengths. From the viewpoint of improving inverse wavelength dispersion, ReA(450) / ReA(550) is preferably 0.70 or higher, more preferably 0.78 or higher, and also preferably 0.95 or lower, more preferably 0.92 or lower.
[0042] The in-plane phase difference value ReA(λ) can be adjusted by the thickness dA of the phase difference layer 13. Since the in-plane phase difference value ReA(λ) is determined by the above equation (6), to obtain a desired in-plane phase difference value, the three-dimensional refractive index and the film thickness dA should be adjusted.
[0043] When the phase difference layer 13 is a stretched film, the thickness of the phase difference layer 13 is usually 5 μm or more and 200 μm or less, preferably 10 μm or more and 80 μm or less, and more preferably 40 μm or less. When the phase difference layer 13 is a horizontally aligned liquid crystal layer, the thickness of the phase difference layer 13 is preferably 0.1 μm or more, more preferably 0.2 μm or more, and also preferably 3 μm or less, and more preferably 2 μm or less.
[0044] The phase difference layer 13 may be formed by stacking multiple layers such that the angle between the slow axes of each layer is an arbitrary angle, such as a combination of a layer having a phase difference characteristic of λ / 4 and a layer having a phase difference characteristic of λ / 2, so that the in-plane phase difference value ReA(550) as a whole satisfies the relationship of equation (4) and ReA(450) / ReA(550) satisfies the relationship of equation (3). When the phase difference layer 13 is a laminate formed by stacking a layer having a phase difference characteristic of λ / 4 and a layer having a phase difference characteristic of λ / 2, for example, a laminate formed so that the angle between the slow axes of each layer is 50° or more and 70° or less can be suitably used.
[0045] Details regarding the materials constituting the phase difference layer 13, the method for forming the phase difference layer 13, etc., will be described later.
[0046] (Method of manufacturing optical laminates) Figure 2 is a schematic diagram illustrating an example of a method for manufacturing the optical laminate 1 shown in Figure 1. The optical laminate 1 shown in Figure 1 can be manufactured by laminating each of the above-mentioned layers via a bonding layer as needed. As shown in Figure 2, when manufacturing the optical laminate 1 by so-called roll-to-roll lamination, where a long film is continuously conveyed and laminated, for example, a first laminate 20 containing a dye-containing layer 11 and a polarizing layer 12 and a phase difference layer 13 can be laminated via a bonding layer while being continuously conveyed in the direction of the arrow in Figure 2. If the phase difference layer 13 is a horizontally aligned liquid crystal layer, a laminate having a horizontally aligned liquid crystal layer on a substrate may be laminated to the first laminate 20.
[0047] By manufacturing the optical laminate 1 using a roll-to-roll method, the manufacturing process for the optical laminate 1 can be shortened, and the inclusion of foreign matter between layers can be prevented, resulting in an optical laminate 1 with excellent visibility.
[0048] (display device) The optical laminate 1 can be used in a display device. An organic EL display device is preferred as the display device. The optical laminate 1 is provided on the viewing side of the display device panel, and in the display device, it is preferable that the dye-containing layer 11 is positioned on the viewing side of the polarizing layer 12. This makes it possible to provide a display device that suppresses the hue difference between the front reflection hue and the oblique reflection hue in black display.
[0049] [Embodiment 2] (optical laminate) Figure 3 is a schematic cross-sectional view showing an optical laminate according to another embodiment of the present invention. As shown in Figure 3, the optical laminate 5 comprises a dye-containing layer 11, a polarizing layer 12, a phase difference layer 13 having an in-plane phase difference, and a vertically aligned liquid crystal layer 17 in this order. It is preferable that the optical laminate 5 constitutes an elliptical polarizer (including the case of a circular polarizer) with the polarizing layer 12 and the phase difference layer 13. The optical laminate 5 may further have a hard coat layer 16 or a protective film 15 on the side of the dye-containing layer 11 opposite to the polarizing layer 12. The optical laminate 5 shown in Figure 3 has both a hard coat layer 16 and a protective film 15. When the optical laminate 5 has both a hard coat layer 16 and a protective film 15, it is preferable that the protective film 15 and the hard coat layer 16 are provided in this order from the dye-containing layer 11 side.
[0050] It is preferable that each layer constituting the optical laminate 5 is laminated via a bonding layer, which is an adhesive layer or a bonding agent layer. When the optical laminate 5 has both a hard coat layer 16 and a protective film 15, it is preferable that the protective film 15 and the hard coat layer 16 are in direct contact without a bonding layer in between. In the optical laminate 5, it is preferable that there is a bonding agent layer between the phase difference layer 13 and the vertically aligned liquid crystal layer 17, and that the bonding agent layer is in direct contact with the phase difference layer 13 and the vertically aligned liquid crystal layer 17. It is preferable that the bonding agent layer is a cured product layer of an ultraviolet-curable adhesive composition, which will be described later.
[0051] When the dye-containing layer 11, the polarizing layer 12, the phase difference layer 13, and the vertically aligned liquid crystal layer 17 are layers formed using liquid crystal compounds such as polymerizable liquid crystal compounds, the optical laminate 5 may have an alignment film for restricting the orientation of the liquid crystal compounds so as to be in direct contact with the layers formed using the liquid crystal compounds, or it may have a substrate for forming the layers or alignment film formed using the liquid crystal compounds. The layers or alignment film formed using the liquid crystal compounds and the substrate can be provided in direct contact with each other.
[0052] In the optical laminate 5, the angle between the absorption axis of the polarizing layer 12 and the slow phase axis of the phase difference layer 13 is preferably within the range of 45°±5°. The above angle may be within the range of 45°±3° or may be 45°.
[0053] The optical laminate 5 can be used in a display device, and is particularly suitable for use in an organic EL display device. In the display device, the optical laminate 5 is arranged such that the dye-containing layer 11 is on the viewing side of the polarizing layer 12. In a display device incorporating the optical laminate 5 in this arrangement, the degree of coloration of the reflected light from an oblique direction of the display device (oblique reflection hue) can be improved when displaying black.
[0054] The dye-containing layer 11, the polarizing layer 12, and the phase difference layer 13 can be those described in the previous embodiment, and their arrangement can also be as described in the previous embodiment.
[0055] (Vertical alignment liquid crystal layer) The vertically aligned liquid crystal layer 17 is a cured layer in which polymerizable liquid crystal compounds are oriented in the stacking direction of the optical laminate 5. The vertically aligned liquid crystal layer 17 may contain a dichroic dye, but it is preferable that it does not contain at least this dichroic dye, and more preferably that it does not contain any dichroic dyes at all.
[0056] Here, the phase difference value RthC(λ) in the thickness direction of the vertically aligned liquid crystal layer 17 at wavelength λ is expressed by the following equation (7). RthC(λ) =((nxC(λ)+nyC(λ)) / 2-nzC(λ))×dC (7) [In formula (7), nxC(λ) represents the principal refractive index at wavelength λnm within the plane of the vertically aligned liquid crystal layer 17. nyC(λ) represents the refractive index at a wavelength λnm in the direction perpendicular to nxC(λ) within the same plane as nxC(λ). nzC(λ) represents the refractive index at wavelength λnm in the thickness direction of the vertically aligned liquid crystal layer 17, and if nxC(λ) = nyC(λ), then nxC(λ) can be the refractive index in any direction within the plane of the vertically aligned liquid crystal layer 17. dC indicates the film thickness of the vertically aligned liquid crystal layer 17.
[0057] RthC(450) / RthC(550) is not particularly limited, but is preferably 0.70 or higher, more preferably 0.75 or higher, even more preferably 0.80 or higher, and may be 1.00 or higher, 1.10 or higher, or 1.20 or higher. It is also preferably 0.95 or lower, even more preferably 0.92 or lower, and particularly preferably 0.90 or lower.
[0058] In the vertically aligned liquid crystal layer 17, it is preferable that the polymerizable liquid crystal compound is oriented with high order in the stacking direction. This enhances the effect of improving the oblique reflection hue when displaying black in the display device incorporating the optical laminate 5. To facilitate obtaining this effect, the RthC(550) of the vertically aligned liquid crystal layer 17 is preferably in the range of -120 nm to -30 nm. From the viewpoint of further improving the above effect, the RthC(550) of the vertically aligned liquid crystal layer 17 is more preferably -100 nm or more, even more preferably -90 nm or more, particularly preferably -80 nm or more, and more preferably -40 nm or less, and even more preferably -50 nm or less.
[0059] The phase difference value RthC(λ) in the thickness direction can be adjusted by the thickness dC of the vertically aligned liquid crystal layer 17. Since the phase difference value RthC(λ) in the thickness direction is determined by the above equation (7), in order to obtain a desired phase difference value RthC(λ) in the thickness direction, it is sufficient to adjust the three-dimensional refractive index and the film thickness dC.
[0060] As described above, in a display device in which the optical laminate 5 is incorporated such that the dye-containing layer 11 is on the visible side of the polarizing layer 12, the vertically aligned liquid crystal layer 17 can be used to improve the oblique reflection hue when the display device is showing black. Therefore, in a display device incorporating the optical laminate 5, the oblique reflection hue when the display device is showing black can be improved.
[0061] On the other hand, even if a laminate with the same layer structure as the optical laminate 5 is used, except that the dye-containing layer 11 is omitted and a layer containing the dichroic dye in the vertically aligned liquid crystal layer 17 (hereinafter sometimes referred to as the "dye-containing liquid crystal layer") is used, the oblique reflection hue when the display device is showing black can be improved. However, the absorbance and absorption wavelength of the dye-containing liquid crystal layer and the phase difference value Rth in the thickness direction of the dye-containing liquid crystal layer are interrelated parameters. Therefore, for example, if only the thickness of the dye-containing liquid crystal layer is increased or decreased in order to adjust the phase difference value Rth in the thickness direction of the dye-containing liquid crystal layer, a large increase or decrease will occur in the absorbance, and coloring may be observed when viewed from an oblique angle when the display device is showing white. Also, for example, if the concentration of the dichroic dye contained in the dye-containing liquid crystal layer is changed in order to adjust the absorbance of the dichroic dye, the phase difference value Rth in the thickness direction of the dye-containing liquid crystal layer will fluctuate, which may cause a decrease in contrast when viewed from an oblique angle when the display device is showing black. Furthermore, because the magnitude of the phase difference of reflected light reflected obliquely from the metal electrode surface differs depending on the type of display panel, the optimal phase difference value Rth in the thickness direction varies, and therefore needs to be adjusted according to the structure of the display device. Consequently, in order to improve the oblique reflection hue using only a dye-containing liquid crystal layer, it is necessary to adjust the thickness of the dye-containing liquid crystal layer and the concentration of the dichroic dye according to the structure of the display device, which presents the problem of complicated fabrication of the dye-containing liquid crystal layer.
[0062] In contrast, in the optical laminate 5 of this embodiment, the dye-containing layer 11 absorbs colored light from an oblique direction, and the vertically aligned liquid crystal layer 17 improves the reflected hue by adjusting the phase difference value of the phase difference layer 13 in the oblique direction using the phase difference value Rth in the thickness direction. Thus, in the optical laminate 5, two independent layers share the two functions described above. Therefore, to adjust the absorbance and absorption wavelength, only the dye-containing layer 11 needs to be adjusted, and to adjust the phase difference value Rth in the thickness direction, only the vertically aligned liquid crystal layer 17 needs to be adjusted. In this way, in the optical laminate 5, the two functions can be adjusted independently in the two independent layers, so the adjustment of the two functions can be made more easily compared to the case where the two functions are adjusted in a single layer, such as the dye-containing liquid crystal layer described above.
[0063] (Method of manufacturing optical laminates) The optical laminate 5 shown in Figure 3 can be manufactured by laminating the optical laminate 1 shown in Figure 1 and a vertically aligned liquid crystal layer 17 via a bonding layer. The bonding layer is preferably an adhesive layer, and more preferably a cured layer of an ultraviolet-curable adhesive composition. The optical laminate 5 may also be manufactured by bonding the optical laminate 1 and a laminate on which a vertically aligned liquid crystal layer 17 is provided on a substrate. The optical laminate 5 is preferably manufactured by roll-to-roll, as described in the manufacturing of the optical laminate 1 in the previous embodiment (Figure 2).
[0064] (display device) The optical laminate 5 can be used in a display device. An organic EL display device is preferred as the display device. The optical laminate 5 is provided on the viewing side of the display device panel, and it is preferable that the dye-containing layer 11 is positioned on the viewing side of the display device, relative to the polarizing layer 12. This makes it possible to provide a display device that suppresses the hue difference between the front reflection hue and the oblique reflection hue in the black display of the display device.
[0065] [Embodiment 3] (optical laminate) Figures 4 and 5 are schematic cross-sectional views showing an optical laminate according to yet another embodiment of the present invention.
[0066] As shown in Figure 4, the optical laminate 6 comprises a dye-containing layer 11, a polarizing layer 12, and a phase difference layer 13 having an in-plane phase difference in this order. Preferably, the optical laminate 6 constitutes an elliptical polarizer (including cases where it is a circular polarizer) with the polarizing layer 12 and the phase difference layer 13. The optical laminate 6 may further have a first hard coat layer 16 and / or a first protective film 15 on the side of the dye-containing layer 11 opposite to the polarizing layer 12. The first hard coat layer 16 and the first protective film 15 correspond to the hard coat layer 16 and protective film 15 described in the previous embodiment, respectively. The optical laminate 6 shown in Figure 4 has both the first hard coat layer 16 and the first protective film 15. When the optical laminate 6 has both the first hard coat layer 16 and the first protective film 15, it is preferable to have the first protective film 15 and the first hard coat layer 16 in this order from the dye-containing layer 11 side, as shown in Figure 4.
[0067] It is preferable that each layer constituting the optical laminate 6 is laminated via a bonding layer, which is an adhesive layer or a bonding agent layer. When the optical laminate 6 has both a first hard coat layer 16 and a first protective film 15, it is preferable that the first protective film 15 and the first hard coat layer 16 are in direct contact without a bonding layer in between.
[0068] The optical laminate 6 shown in Figure 4 further includes a second hard coat layer 162 and a second protective film 152 between the dye-containing layer 11 and the polarizing layer 12, in that order from the dye-containing layer 11 side. Preferably, the second hard coat layer 162 and the second protective film 152 are in direct contact without an intervening lamination layer. The second hard coat layer 162 is usually laminated to the dye-containing layer 11 via an intervening lamination layer. The second protective film 152 is usually laminated to the polarizing layer 12 via an intervening lamination layer. The intervening lamination layer is an adhesive layer or a bonding agent layer. The second hard coat layer 162, the second protective film 152, and the polarizing layer 12 can constitute a polarizing plate.
[0069] The optical laminate 6 includes a first hard coat layer 16 on the side of the dye-containing layer 11 opposite to the polarizing layer 12, via a first protective film 15, and a second hard coat layer 162 and a second protective film 152 on the polarizing layer 12 side of the dye-containing layer 11, in this order. In such an optical laminate 6, from the viewpoint of improving the crack resistance of the dye-containing layer 11 against impact from the first hard coat layer 16 side, it is preferable that the first hard coat layer 16 has a pencil hardness of HB to 6B when laminated on the first protective film 15, and the second hard coat layer 162 has a pencil hardness of HB to 6B when laminated on the second protective film 152. The pencil hardness of the first hard coat layer 16 and the pencil hardness of the second hard coat layer 162 may be the same. Alternatively, the pencil hardness of the first hard coat layer 16 may be softer or harder than the pencil hardness of the second hard coat layer 162. When the pencil hardness of the first hard coat layer 16 and the pencil hardness of the second hard coat layer 162 are different, the difference is usually 6 levels or less, but it is preferable that it be 2 levels or more from the viewpoint of further improving crack resistance.
[0070] The optical laminate 6 may further have a third hard coat layer between the dye-containing layer 11 and the polarizing layer 12. If the optical laminate 6 comprises a second hard coat layer 162 and a second protective film 152, a third hard coat layer can be provided between the dye-containing layer 11 and the second hard coat layer 162. The third hard coat layer can be provided in direct contact with the dye-containing layer 11 or the alignment film directly in contact with the dye-containing layer 11, and it is preferable that the third hard coat layer and the polarizing layer 12 or the second hard coat layer 162 are laminated via a bonding layer. It is preferable that the bonding layer is in direct contact with the polarizing layer 12 or the second hard coat layer 162 and the third hard coat layer. The pencil hardness of the third hard coat layer may be the same as or different from that of the first hard coat layer 16 or the second hard coat layer 162.
[0071] The optical laminate 6 shown in Figure 4 can be used in a display device. The optical laminate 6 can also be used as a manufacturing intermediate for an optical laminate 7 (Figure 5) which includes, in this order, a vertically aligned liquid crystal layer 17 cured on the phase difference layer 13 side of the optical laminate 6 with polymerizable liquid crystal compounds oriented in the stacking direction of the optical laminate 6.
[0072] The optical laminate 7 shown in Figure 5 has a structure in which an optical laminate 6 and a vertically aligned liquid crystal layer 17 are laminated. In the optical laminate 7, it is preferable that the vertically aligned liquid crystal layer 17 is laminated on the phase difference layer 13 side of the optical laminate 6 via a bonding layer which is an adhesive layer or bonding agent layer.
[0073] The optical laminates 6 and 7 can be used in display devices, and are particularly suitable for use in organic EL display devices. In the display device, the optical laminates 6 and 7 are arranged such that the dye-containing layer 11 is on the viewing side of the polarizing layer 12. In a display device incorporating the optical laminate 6 in the above arrangement, the dye-containing layer 11 can cancel out the coloration of the black image when the black image displayed on the panel is viewed from an oblique direction. This reduces the coloration of the black image when the display device is viewed from an oblique direction. Furthermore, in a display device incorporating the optical laminate 7 in the above arrangement, the degree of coloration of the reflected light from the display device from an oblique direction (oblique reflection hue) can be improved when displaying black.
[0074] The dye-containing layer 11, the polarizing layer 12, the phase difference layer 13, and the vertically aligned liquid crystal layer 17 can be those described in the previous embodiment, and their arrangement can also be as described in the previous embodiment.
[0075] (Method of manufacturing optical laminates) The optical laminate 6 shown in Figure 4 and the optical laminate 7 shown in Figure 5 can be manufactured by laminating each of the above-described layers via a laminating layer as needed. For example, to obtain the optical laminate 6, first, a second laminate containing a first hard coat layer 16, a first protective film 15, a dye-containing layer, and optionally a third hard coat layer is laminated with a polarizing plate containing a second hard coat layer 162, a second protective film 152, and a polarizing layer 12 via a laminating layer to obtain a third laminate. Next, the optical laminate 6 can be obtained by laminating this third laminate with a phase difference layer 13 via a laminating layer. The optical laminate 7 can be manufactured by laminating the optical laminate 6 with a vertically aligned liquid crystal layer 17 via a laminating layer. The optical laminate 7 may also be manufactured by laminating the optical laminate 6 with a laminate on which a vertically aligned liquid crystal layer 17 is provided on a substrate. The optical laminates 6 and 7 are preferably manufactured by roll-to-roll, as described in the manufacturing of the optical laminate 1 in the previous embodiment (Figure 2).
[0076] (display device) The optical laminates 6 and 7 can be used in a display device. An organic EL display device is preferred as the display device. The optical laminates 6 and 7 are provided on the viewing side of the display device panel, and it is preferable that the dye-containing layer 11 is positioned on the viewing side of the display device, relative to the polarizing layer 12. This makes it possible to provide a display device that suppresses the hue difference between the front reflection hue and the oblique reflection hue in the black display of the display device.
[0077] The details of each component used in the optical laminate of this embodiment and their manufacturing methods will be described below. (This dichroic pigment) The dichroic pigment contained in the pigment-containing layer is not particularly limited as long as it is a dichroic pigment having maximum absorption in the wavelength range of 400 nm to 750 nm. The dichroic pigment may be a dye or a pigment. The dichroic pigment contained in the pigment-containing layer may be a combination of two or more dyes, a combination of two or more pigments, or a combination of a dye and a pigment.
[0078] Since the dye-containing layer preferably satisfies the above-mentioned [a1] or [a2], it is preferable to use a dye selected from acridine dyes, oxazine dyes, cyanine dyes, naphthalene dyes, azo dyes, and anthraquinone dyes as the dichroic dye. Among these, it is more preferable to use an azo dye from the viewpoint of orientation. Furthermore, the dichroic dye may exhibit liquid crystalline properties.
[0079] Examples of azo dyes include monoazo dyes, bisazo dyes, trisazo dyes, tetrakisazo dyes, and stilbenazo dyes, with bisazo dyes and trisazo dyes being preferred. For example, the compound represented by formula (i) (hereinafter sometimes referred to as "compound (i)") is an example. K 1 (-N=NK 2 ) p -N=NK 3 (i) [In formula (i), K 1 and K 3 These independently represent an optionally substituted phenyl group, an optionally substituted naphthyl group, or an optionally substituted monovalent heterocyclic group. K 2 This represents a optionally substituted p-phenylene group, an optionally substituted naphthalene-1,4-diyl group, or an optionally substituted divalent heterocyclic group. p represents an integer from 1 to 4. If p is an integer greater than or equal to 2, multiple K 2 They may be the same or different from each other. Within the range where absorption is observed in the visible spectrum, the -N=N- bond may be replaced by -C=C-, -COO-, -NHCO-, or -N=CH- bonds.
[0080] Examples of monovalent heterocyclic groups include groups obtained by removing one hydrogen atom from heterocyclic compounds such as quinoline, thiazole, benzothiazole, thienothiazole, imidazole, benzimidazole, oxazole, and benzoxazole. Examples of divalent heterocyclic groups include groups obtained by removing two hydrogen atoms from the above heterocyclic compounds.
[0081] K 1 and K 3 the phenyl group, naphthyl group and monovalent heterocyclic group in, and K 2 Examples of the substituents optionally possessed by the p-phenylene group, naphthalene-1,4-diyl group and divalent heterocyclic group in include an alkyl group having 1 to 20 carbon atoms, an alkyl group having 1 to 20 carbon atoms and a polymerizable group, an alkenyl group having 1 to 4 carbon atoms; an alkoxy group having 1 to 20 carbon atoms such as a methoxy group, an ethoxy group, a butoxy group; an alkoxy group having 1 to 20 carbon atoms and a polymerizable group; an alkyl fluoride group having 1 to 4 carbon atoms such as a trifluoromethyl group; a cyano group; a nitro group; a halogen atom; a substituted or unsubstituted amino group such as an amino group, a diethylamino group, a pyrrolidino group (the substituted amino group means an amino group having one or two alkyl groups having 1 to 6 carbon atoms, an amino group having one or two alkyl groups having 1 to 6 carbon atoms and a polymerizable group, or an amino group in which two substituted alkyl groups are bonded to each other to form an alkanediyl group having 2 to 8 carbon atoms. The unsubstituted amino group is -NH2.). etc. are mentioned. Here, examples of the above polymerizable group include an acryloyl group, a methacryloyl group, an acryloyloxy group, a methacryloyloxy group and the like.
[0082] Among the compounds (i), compounds represented by any of the following formulas (i-1) to (i-8) are preferred. [Chemical formula] [In formulas (i-1) to (i-8), B 1 ~B 30 independently of one another, represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, a nitro group, a substituted or unsubstituted amino group (the definitions of the substituted amino group and the unsubstituted amino group are as described above), a chlorine atom or a trifluoromethyl group. n1 to n4 independently of one another represent an integer of 0 to 3. When n1 is 2 or more, the plurality of B 2 may be the same as or different from each other, If n2 is 2 or more, multiple B 6 They may be the same or different from each other. If n3 is 2 or more, multiple B 9 They may be the same or different from each other. If n4 is 2 or more, multiple B 14 They may be the same or different from each other.
[0083] As the anthraquinone dye, the compound represented by formula (i-9) is preferred. [ka] [In formula (i-9), R 1 ~R 8 These are, independently of each other, hydrogen atoms, -R x -NH2, -NHR x , -NR x 2, -SR x Alternatively, it represents a halogen atom. R x This represents an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 12 carbon atoms.
[0084] As the oxazone dye, the compound represented by formula (i-10) is preferred. [ka] [In formula (i-10), R 9 ~R 15 These are, independently of each other, hydrogen atoms, -R x -NH2, -NHR x , -NR x 2, -SR x Alternatively, it represents a halogen atom. R x This represents an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 12 carbon atoms.
[0085] As the acridine dye, the compound represented by formula (i-11) is preferred. [ka] [In formula (i-11), R 16 ~R 23 These are, independently of each other, hydrogen atoms, -R x -NH2, -NHR x , -NR x 2, -SR x Alternatively, it represents a halogen atom. R x This represents an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 12 carbon atoms.
[0086] In equations (i-9), (i-10), and (i-11), R x Examples of alkyl groups having 1 to 6 carbon atoms include methyl, ethyl, propyl, butyl, pentyl, and hexyl groups, while examples of aryl groups having 6 to 12 carbon atoms include phenyl, toluyl, xylyl, and naphthyl groups.
[0087] As cyanine dyes, compounds represented by formula (i-12) and compounds represented by formula (i-13) are preferred. [ka] [In formula (i-12), D 1 and D 2 These represent a base that is independently expressed by any of the equations (i-12a) to (i-12d). [ka] n5 represents an integer between 1 and 3.
[0088] [ka] [In formula (i-13), D 3 and D 4These represent a base that is independently expressed by any of the equations (i-13a) to (i-13h). [ka] n6 represents an integer between 1 and 3.
[0089] From the viewpoint of orientation, the dye-containing layer preferably contains at least one azo dye as the dichroic dye. The weight-average molecular weight of the dichroic dye is usually 300 to 2000, preferably 400 to 1000.
[0090] The content of the dichroic dye in the composition forming the dye-containing layer can be appropriately determined depending on the type of dichroic dye, etc. When the dye-containing layer contains a cured product of a polymerizable liquid crystal compound, the content of the dichroic dye in the composition is preferably 0.1 to 20 parts by mass, more preferably 0.1 to 10 parts by mass, and even more preferably 0.1 to 5 parts by mass, per 100 parts by mass of the polymerizable liquid crystal compound. When the content of the dichroic dye is within the above range, it is possible to control the absorbance so as not to interfere with the white display of the display device and to compensate for the reflected hue from oblique directions. Furthermore, it is possible to obtain a cured product of a polymerizable liquid crystal compound that does not easily disrupt the orientation of the polymerizable liquid crystal compound and has a high degree of orientational order.
[0091] (Polymerizable liquid crystal compounds and polymerizable liquid crystal compositions for forming a dye-containing layer) The dye-containing layer may include a cured product in which the polymerizable liquid crystal compound is oriented in the stacking direction of the optical laminate. The polymerizable liquid crystal compound is a liquid crystal compound having polymerizable groups, and it is preferable that the polymerizable groups are photopolymerizable groups. The polymerizable liquid crystal compound is not particularly limited as long as it can form a dye-containing layer that satisfies the above formulas (1) and (2), and for example, polymerizable liquid crystal compounds conventionally known in the field of phase difference films can be used.
[0092] A polymerizable group is a group that can participate in a polymerization reaction. A photopolymerizable group is a polymerizable group that can participate in a polymerization reaction by reaction-active species generated from a photopolymerization initiator, such as active radicals or acids. Examples of photopolymerizable groups include vinyl groups, vinyloxy groups, 1-chlorovinyl groups, isopropenyl groups, 4-vinylphenyl groups, acryloyloxy groups, methacryloyloxy groups, oxyranyl groups, and oxetanyl groups. Among these, acryloyloxy groups, methacryloyloxy groups, vinyloxy groups, oxyranyl groups, and oxetanyl groups are preferred, with acryloyloxy groups being more preferred. The liquid crystalline properties exhibited by the polymerizable liquid crystal compound may be thermotropic liquid crystal or lyotropic liquid crystal, but thermotropic liquid crystal is preferred because it allows for precise control of film thickness. Furthermore, the phase order structure in the thermotropic liquid crystal may be either a nematic liquid crystal or a smectic liquid crystal. From the viewpoint of reducing the value of AxC and increasing the value of AxC(z=60) / AxC in the above-mentioned equations (1) and (2), smectic liquid crystal is preferred. When the value of AxC is small and the value of AxC(z=60) / AxC is large, the oblique reflection hue can be effectively improved while maintaining good white display of the above-mentioned display device. Polymerizable liquid crystal compounds can be used alone or in combination of two or more types.
[0093] Polymerizable liquid crystal compounds generally include polymerizable liquid crystal compounds that exhibit positive wavelength dispersion and polymerizable liquid crystal compounds that exhibit negative wavelength dispersion. It is possible to use only one of these polymerizable liquid crystal compounds, or to use a mixture of both polymerizable liquid crystal compounds.
[0094] The polymerizable liquid crystal compound exhibiting inverse wavelength dispersion is preferably a compound having the following characteristics (A) to (D). (A) A compound that can form a nematic or smectic phase. (B) The polymerizable liquid crystal compound has π electrons along the long axis (a). (C) It has π electrons in a direction intersecting the long axis direction (a) [intersecting direction (b)]. (D) The π electron density in the long axis direction (a) of a polymerizable liquid crystal compound defined by the following formula (ia), where N(πa) is the total number of π electrons present in the long axis direction (a) and N(Aa) is the total molecular weight present in the long axis direction: D(πa)=N(πa) / N(Aa) (ia) The π electron density in the cross direction (b) of a polymerizable liquid crystal compound defined by the following formula (iib), where N(πb) is the total number of π electrons present in the cross direction (b) and N(Ab) is the total molecular weight present in the cross direction (b): D(πb)=N(πb) / N(Ab) (iib) And, equation (iii) 0≦〔D(πa) / D(πb)〕<1 (iiic) This relationship exists [that is, the π electron density in the intersecting direction (b) is greater than the π electron density in the long axis direction (a)]. Furthermore, polymerizable liquid crystal compounds having π electrons on the long axis and in the direction intersecting it, as described above, form a T-shaped structure, for example.
[0095] In the characteristics described in (A) to (D) above, the major axis direction (a) and the number of π electrons N are defined as follows. • The longitudinal axis direction (a) is, for example, the longitudinal axis direction of the rod-shaped structure of the compound. The number of π electrons N(πa) located along the long axis (a) does not include the π electrons that are lost due to polymerization reactions. The number of π electrons N(πa) located along the long axis (a) is the total number of π electrons on the long axis and their conjugate π electrons, and includes, for example, the number of π electrons in a ring located along the long axis (a) that satisfies Hückel's rule. The number of π electrons N(πb) present in the intersecting direction (b) does not include the π electrons that are lost due to polymerization reactions. Polymerizable liquid crystal compounds that satisfy the above conditions have a mesogenic structure in the long axis direction. This mesogenic structure causes the liquid crystal phase (nematic phase, smectic phase) to manifest.
[0096] Polymerizable liquid crystal compounds satisfying the above conditions (A) to (D) can be coated onto a substrate or an oriented film and heated above the phase transition temperature to form a nematic or smectic phase. In the nematic or smectic phase formed by the orientation of these polymerizable liquid crystal compounds, the long axes of the polymerizable liquid crystal compounds are usually oriented parallel to each other, and this long axis direction becomes the orientation direction of the nematic phase. When such polymerizable liquid crystal compounds are made into a film and polymerized in the nematic or smectic phase state, a polymer film can be formed consisting of polymers polymerized in a state oriented along the long axis (a). This polymer film absorbs ultraviolet light by π electrons along the long axis (a) and π electrons along the intersecting direction (b). Here, the wavelength of maximum absorption of ultraviolet light absorbed by π electrons along the intersecting direction (b) is denoted as λbmax. λbmax is usually 300 nm to 400 nm. The density of π electrons satisfies the above equation (iiic), and since the π electron density in the crossing direction (b) is greater than the π electron density in the long axis direction (a), the polymer film absorbs linearly polarized ultraviolet light (wavelength λbmax) with a vibration plane in the crossing direction (b) greater than the absorption of linearly polarized ultraviolet light (wavelength λbmax) with a vibration plane in the long axis direction (a). The ratio (ratio of absorbance in the crossing direction (b) of linearly polarized ultraviolet light / absorbance in the long axis direction (a)) is, for example, greater than 1.0, preferably 1.2 or more, usually 30 or less, and for example 10 or less.
[0097] Polymerizable liquid crystal compounds possessing the above characteristics generally exhibit inverse wavelength dispersion. Specifically, examples include compounds represented by the following formula (X). [ka]
[0098] In formula (X), Ar represents a divalent group having an aromatic group which may have substituents. Here, an aromatic group refers to one whose ring structure has [4n+2] π electrons according to Hückel's rule, and may have two or more Ar groups, such as those exemplified in (Ar-1) to (Ar-23) described later, via a divalent linking group. Here, n represents an integer. When a ring structure is formed by including heteroatoms such as -N= or -S-, it also includes cases where the non-covalent electron pairs on these heteroatoms satisfy Hückel's rule and are aromatic. Preferably, the aromatic group contains at least one of nitrogen, oxygen, and sulfur atoms. The divalent group Ar may contain one or more aromatic groups. When there is one aromatic group, the divalent group Ar may be a divalent aromatic group which may have substituents. If the divalent group Ar contains two or more aromatic groups, these two or more aromatic groups may be bonded to each other by single bonds, divalent bonding groups such as -CO-O- or -O-. G 1 and G 2 Each of these independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group. Here, the hydrogen atoms contained in the divalent aromatic group or divalent alicyclic hydrocarbon group may be substituted with halogen atoms, C1-C4 alkyl groups, C1-C4 fluoroalkyl groups, C1-C4 alkoxy groups, cyano groups, or nitro groups, and the carbon atoms constituting the divalent aromatic group or divalent alicyclic hydrocarbon group may be substituted with oxygen atoms, sulfur atoms, or nitrogen atoms. L 1 , L 2 B 1 and B 2 Each of these is independently a single bond or a divalent linking group. k and l each represent integers from 0 to 3 independently, satisfying the relationship 1 ≤ k + l. Here, if 2 ≤ k + l, then B 1 and B 2 , G 1 and G 2 These elements may be identical to each other, or they may be different. E 1 and E 2Each of these independently represents an alkanediyl group having 1 to 17 carbon atoms, with an alkanediyl group having 4 to 12 carbon atoms being more preferred. Furthermore, the hydrogen atoms in the alkanediyl group may be substituted with halogen atoms, and the -CH2- in the alkanediyl group may be substituted with -O-, -S-, -SiH2-, or -C(=O)-. P 1 and P 2 Each of these independently represents a polymerizable group or a hydrogen atom, and at least one of them is a polymerizable group.
[0099] G 1 and G 2 Each of these is independently preferably a 1,4-phenylenediyl group which may be substituted with at least one substituent selected from the group consisting of a halogen atom and an alkyl group having 1 to 4 carbon atoms, or a 1,4-cyclohexanediyl group which may be substituted with at least one substituent selected from the group consisting of a halogen atom and an alkyl group having 1 to 4 carbon atoms, more preferably a methyl-substituted 1,4-phenylenediyl group, an unsubstituted 1,4-phenylenediyl group, or an unsubstituted 1,4-trans-cyclohexanediyl group, and particularly preferably an unsubstituted 1,4-phenylenediyl group or an unsubstituted 1,4-trans-cyclohexandiyl group. Also, there are multiple G 1 and G 2 Preferably, at least one of them is a divalent alicyclic hydrocarbon group, and L 1 or L 2 G that joins 1 and G 2 It is more preferable that at least one of these is a divalent alicyclic hydrocarbon group.
[0100] L 1 and L 2 Each of these is independently, preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a1 Ure a2 -, -R a3 COOR a4 -, -R a5 OCOR a6 -, -R a7OC=OOR a8 -, -N=N-, -CR c =CR d -, or -C≡C-. Here, R a1 ~R a8 each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms, and R c and R d represent an alkyl group having 1 to 4 carbon atoms or a hydrogen atom. L 1 and L 2 each independently is more preferably a single bond, -OR a2-1 -, -CH2-, -CH2CH2-, -COOR a4-1 -, or -OCOR a6-1 -. Here, R a2-1 , R a4-1 [[ID=2,8]]R a6-1 each independently represents any one of a single bond, -CH2-, -CH2CH2-. L 1 and L 2 each independently is even more preferably a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, or -OCO-.
[0101] B 1 and B 2 each independently is preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a9 OR a10 -, -R a11 COOR a12 -, -R a13 OCOR a14 -, or -R a15 OC=OOR a16 -. Here, R a9 ~R a16 each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms. B 1 and B 2 each independently is more preferably a single bond, -OR a10-1 -, -CH2-, -CH2CH2-, -COOR a12-1 -, or -OCOR a14-1 -. Here, R a10-1 , R a12-1 , R a14-1Each of these independently represents either a single bond, -CH2-, or -CH2CH2-. 1 and B 2 Each of these is independently, and more preferably, a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, -OCO-, or OCOCH2CH2-.
[0102] From the viewpoint of exhibiting inverse wavelength dispersion, k and l are preferably in the range of 2 ≤ k + l ≤ 6, preferably k + l = 4, and more preferably k = 2 and l = 2. A symmetric structure is preferred when k = 2 and l = 2.
[0103] P 1 or P 2 Examples of polymerizable groups represented by include epoxy groups, vinyl groups, vinyloxy groups, 1-chlorovinyl groups, isopropenyl groups, 4-vinylphenyl groups, acryloyloxy groups, methacryloyloxy groups, oxyranyl groups, and oxetanyl groups. Among these, acryloyloxy groups, methacryloyloxy groups, vinyloxy groups, oxyranyl groups, and oxetanyl groups are preferred, with acryloyloxy groups being more preferred.
[0104] It is preferable that Ar has at least one selected from an aromatic hydrocarbon ring which may have substituents, an aromatic heterocycle which may have substituents, and an electron-withdrawing group. Examples of the aromatic hydrocarbon ring include a benzene ring, a naphthalene ring, an anthracene ring, etc., with benzene rings and naphthalene rings being preferred. Examples of the aromatic heterocycle include a furan ring, a benzofuran ring, a pyrrole ring, an indole ring, a thiophene ring, a benzothiophene ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, a triazole ring, a triazine ring, a pyrroline ring, a pyrodazole ring, an imidazole ring, a pyrazole ring, a thiazole ring, a benzothiazole ring, a thienothiazole ring, an oxazole ring, a benzoxazole ring, and a phenantholine ring, etc. Among these, it is preferable to have a thiazole ring, a benzothiazole ring, or a benzofuran ring, and it is even more preferable to have a benzothiazole group. Furthermore, if Ar contains a nitrogen atom, it is preferable that the nitrogen atom has π electrons.
[0105] In formula (X), the total number of π electrons Nπ contained in the divalent aromatic group represented by Ar is preferably 8 or more, more preferably 10 or more, even more preferably 14 or more, and particularly preferably 16 or more. It is also preferably 30 or less, more preferably 26 or less, and even more preferably 24 or less.
[0106] Examples of aromatic groups represented by Ar include the following groups: [ka]
[0107] In equations (Ar-1) to (Ar-23), the asterisk (*) indicates a connecting part, Z 0 , Z 1 and Z 2 Each of these independently represents a hydrogen atom, a halogen atom, a C1-C12 alkyl group, a cyano group, a nitro group, a C1-C12 alkylsulfinyl group, a C1-C12 alkylsulfonyl group, a carboxyl group, a C1-C12 fluoroalkyl group, a C1-C12 alkoxy group, a C1-C12 alkylthio group, a C1-C12 N-alkylamino group, a C2-C12 N,N-dialkylamino group, a C1-C12 N-alkylsulfamoyl group, or a C2-C12 N,N-dialkylsulfamoyl group. 0 , Z 1 and Z 2 It may contain polymerizable groups.
[0108] Q 1 and Q 2 Each of these is independently of -CR 2’ R 3’ -, -S-, -NH-, -NR 2’ - represents -CO- or -O-, R 2’ and R 3’ Each of these independently represents either a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
[0109] J 1 , and J2 Each of these independently represents either a carbon atom or a nitrogen atom.
[0110] Y 1 , Y 2 and Y 3 Each of these independently represents an optionally substituted aromatic hydrocarbon group or an aromatic heterocyclic group.
[0111] W 1 and W 2 Each of these independently represents a hydrogen atom, a cyano group, a methyl group, or a halogen atom, and m represents an integer from 0 to 6.
[0112] Y 1 , Y 2 and Y 3 Examples of aromatic hydrocarbon groups in this context include C6-C20 aromatic hydrocarbon groups such as phenyl, naphthyl, anthuryl, phenanthuryl, and biphenyl groups, with phenyl and naphthyl groups being preferred and phenyl groups being more preferred. Examples of aromatic heterocyclic groups include C4-C20 aromatic heterocyclic groups containing at least one heteroatom such as a nitrogen atom, oxygen atom, or sulfur atom, such as furyl, pyrrolyl, thienyl, pyridinyl, thiazolyl, and benzothiazolyl groups, with furyl, thienyl, pyridinyl, thiazolyl, and benzothiazolyl groups being preferred.
[0113] Y 1 , Y 2 and Y 3 Each of these may independently be a substituted polycyclic aromatic hydrocarbon group or a polycyclic aromatic heterocyclic group. A polycyclic aromatic hydrocarbon group refers to a fused polycyclic aromatic hydrocarbon group or a group derived from an aromatic ring assembly. A polycyclic aromatic heterocyclic group refers to a fused polycyclic aromatic heterocyclic group or a group derived from an aromatic ring assembly.
[0114] Z 0 , Z 1 and Z 2 Each of these is preferably independently a hydrogen atom, a halogen atom, a C1-C12 alkyl group, a cyano group, a nitro group, or a C1-C12 alkoxy group, Z 0A hydrogen atom, an alkyl group having 1 to 12 carbon atoms, and a cyano group are more preferably Z 1 and Z 2 Hydrogen atoms, fluorine atoms, chlorine atoms, methyl groups, and cyano groups are more preferred. Also, Z 0 , Z 1 and Z 2 It may contain polymerizable groups.
[0115] Q 1 and Q 2 -NH-, -S-, -NR 2’ -, -O- is preferred, R 2’ A hydrogen atom is preferred. Among these, -S-, -O-, and -NH- are particularly preferred.
[0116] Among formulas (Ar-1) to (Ar-23), formulas (Ar-6) and (Ar-7) are preferred from the viewpoint of molecular stability.
[0117] In equations (Ar-16) to (Ar-23), Y 1 This is the nitrogen atom and Z to which it is bonded. 0 It may also form an aromatic heterocyclic group. Examples of aromatic heterocyclic groups that Ar may have include those mentioned above, such as a pyrrole ring, imidazole ring, pyrroline ring, pyridine ring, pyrazine ring, pyrimidine ring, indole ring, quinoline ring, isoquinoline ring, purine ring, pyrrolidine ring, etc. This aromatic heterocyclic group may have substituents. Also, Y 1 This is the nitrogen atom and Z to which it is bonded. 0 In addition, the above-mentioned substituted polycyclic aromatic hydrocarbon groups or polycyclic aromatic heterocyclic groups may also be used. Examples include benzofuran rings, benzothiazole rings, benzoxazole rings, and the like.
[0118] Furthermore, as the polymerizable liquid crystal compound that forms the dye-containing layer, for example, a compound containing a group represented by the following formula (Y) (hereinafter sometimes referred to as "polymerizable liquid crystal compound (Y)") may be used. Polymerizable liquid crystal compound (Y) generally tends to exhibit positive wavelength dispersion. Polymerizable liquid crystal compounds can be used alone or in combination of two or more types.
[0119] P11-B11-E11-B12-A11-B13- (Y) [In formula (Y), P11 represents a polymerizable group. A11 represents a divalent alicyclic hydrocarbon group or a divalent aromatic hydrocarbon group. The hydrogen atoms in the divalent alicyclic hydrocarbon group and the divalent aromatic hydrocarbon group may be substituted with halogen atoms, C1-C6 alkyl groups, C1-C6 alkoxy groups, cyano groups, or nitro groups, and the hydrogen atoms in the C1-C6 alkyl groups and the C1-C6 alkoxy groups may be substituted with fluorine atoms. B11 is -O-, -S-, -CO-O-, -O-CO-, -O-CO-O-, -CO-NR 16 -, -NR 16 R represents -CO-, -CO-, -CS-, or a single bond. 16 This represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. B12 and B13 are independently -C≡C-, -CH=CH-, -CH2-CH2-, -O-, -S-, -C(=O)-, -C(=O)-O-, -OC(=O)-, -OC(=O)-O-, -CH=N-, -N=CH-, -N=N-, -C(=O)-NR 16 -, -NR 16 -C(=O)-, -OCH2-, -OCF2-, -CH2O-, -CF2O-, -CH=CH-C(=O)-O-, -OC(=O)-CH=CH-, or a single bond. E11 represents an alkanediyl group having 1 to 12 carbon atoms. The hydrogen atoms in the alkanediyl group may be substituted with an alkoxy group having 1 to 5 carbon atoms, and the hydrogen atoms in the alkoxy group may be substituted with a halogen atom. Furthermore, the -CH2- group constituting the alkanediyl group may be replaced with -O- or -CO-.
[0120] The number of carbon atoms in the aromatic hydrocarbon group and alicyclic hydrocarbon group of A11 is preferably in the range of 3 to 18, more preferably in the range of 5 to 12, and particularly preferably 5 or 6. As A11, cyclohexane-1,4-diyl group and 1,4-phenylene group are preferred.
[0121] As E11, a linear alkanediyl group having 1 to 12 carbon atoms is preferred. The -CH2- group constituting the alkanediyl group may be replaced with -O-. Specifically, examples include linear alkanediyl groups having 1 to 12 carbon atoms, such as methylene group, ethylene group, propane-1,3-diyl group, butane-1,4-diyl group, pentane-1,5-diyl group, hexane-1,6-diyl group, heptane-1,7-diyl group, octane-1,8-diyl group, nonane-1,9-diyl group, decane-1,10-diyl group, undecane-1,11-diyl group, and dodecane-1,12-diyl group; and -CH2-CH2-O-CH2-CH2-, -CH2-CH2-O-CH2-CH2-O-CH2-CH2-, and -CH2-CH2-O-CH2-CH2-O-CH2-CH2-. For B11, -O-, -S-, -CO-O-, and -O-CO- are preferred, with -CO-O- being the most preferred among them. For B12 and B13, independently, -O-, -S-, -C(=O)-, -C(=O)-O-, -OC(=O)-, and -OC(=O)-O- are preferred, with -O- or -OC(=O)-O- being more preferred.
[0122] As the polymerizable group represented by P11, a radical polymerizable group or a cationic polymerizable group is preferable in terms of having high polymerization reactivity, particularly high photopolymerization reactivity. Since it is easy to handle and the production of the liquid crystal compound itself is also easy, the polymerizable group is preferably a group represented by the following formulas (P-11) to (P-15).
Chemical formula
[0123] Specific examples of the group represented by formulas (P-11) to (P-15) include groups represented by the following formulas (P-16) to (P-20).
Chemical formula
[0124] P11 is preferably a group represented by formulas (P-14) to (P-20), and more preferably a vinyl group, a p-stilbene group, an epoxy group or an oxetanyl group. It is even more preferable that the group represented by P11-B11- is an acryloyloxy group or a methacryloyloxy group.
[0125] Examples of the polymerizable liquid crystal compound (Y) include compounds represented by formula (I), formula (II), formula (III), formula (IV), formula (V) or formula (VI). P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-A14-B16-E12-B17-P12 (I) P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-A14-F11 (II) P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-E12-B17-P12 (III) P11-B11-E11-B12-A11-B13-A12-B14-A13-F11 (IV) P11-B11-E11-B12-A11-B13-A12-B14-E12-B17-P12 (V) P11-B11-E11-B12-A11-B13-A12-F11 (VI) [In equations (I) to (VI), A12 to A14 are each independently synonymous with A11, B14 to B16 are each independently synonymous with B12, B17 is synonymous with B11, and E12 is synonymous with E11. F11 represents a hydrogen atom, a C1-C13 alkyl group, a C1-C13 alkoxy group, a cyano group, a nitro group, a trifluoromethyl group, a dimethylamino group, a hydroxyl group, a methylol group, a formyl group, a sulfo group (-SO3H), a carboxyl group, a C1-C10 alkoxycarbonyl group, or a halogen atom, and the -CH2- group constituting the alkyl group and alkoxy group may be replaced with -O-.
[0126] Specific examples of polymerizable liquid crystal compounds (Y) include compounds having polymerizable groups among the compounds described in "3.8.6 Network (Fully Crosslinked Type)" and "6.5.1 Liquid Crystal Materials b. Polymerizable Nematic Liquid Crystal Materials" of the Liquid Crystal Handbook (edited by the Liquid Crystal Handbook Editorial Committee, published by Maruzen Co., Ltd. on October 30, 2000), as well as polymerizable liquid crystals described in Japanese Patent Publication No. 2010-31223, Japanese Patent Publication No. 2010-270108, Japanese Patent Publication No. 2011-6360, and Japanese Patent Publication No. 2011-207765.
[0127] Specific examples of polymerizable liquid crystal compounds (Y) include compounds represented by the following formulas (I-1) to (I-4), (II-1) to (II-4), (III-1) to (III-26), (IV-1) to (IV-26), (V-1) to (V-2), and (VI-1) to (VI-6). In the following formulas, k1 and k2 each independently represent integers from 2 to 12. These polymerizable liquid crystal compounds (Y) are preferred in terms of their ease of synthesis and availability.
[0128]
change
[0129]
change
[0130]
change
[0131]
change
[0132]
change
[0133]
change
[0134]
change
[0135]
change
[0136]
change
[0137] By using a polymerizable liquid crystal compound exhibiting smectic liquid crystal properties, a dye-containing layer with a high degree of orientational order can be formed. When the degree of orientational order is high, the value of AxC in formulas (1) and (2) above is small, and the value of AxC(z=60) / AxC is large. When a polymerizable liquid crystal compound exhibiting smectic liquid crystal properties is used as the polymerizable liquid crystal compound for forming the dye-containing layer, it is more preferable that the polymerizable liquid crystal compound is a higher-order smectic phase (higher-order smectic liquid crystal state) from the viewpoint of achieving a higher degree of orientational order. Here, the higher-order smectic phase refers to smectic B phase, smectic D phase, smectic E phase, smectic F phase, smectic G phase, smectic H phase, smectic I phase, smectic J phase, smectic K phase, and smectic L phase, and among these, smectic B phase, smectic F phase, and smectic I phase are more preferable. The liquid crystalline properties can be either thermotropic or lyotropic, but thermotropic liquid crystalline properties are preferred because they allow for precise control of film thickness. Furthermore, the polymerizable liquid crystal compound exhibiting smectic liquid crystalline properties may be a monomer, an oligomer formed by polymerization of polymerizable groups, or a polymer.
[0138] A polymerizable liquid crystal compound exhibiting smectic liquid crystal properties is a liquid crystal compound having at least one polymerizable group, and from the viewpoint of improving the heat resistance of the dye-containing layer, it is preferable that the liquid crystal compound has two or more polymerizable groups. Examples of polymerizable groups include (meth)acryloyloxy group, vinyl group, vinyloxy group, 1-chlorovinyl group, isopropenyl group, 4-vinylphenyl group, oxiranyl group, oxetanyl group, etc., but among these, it is preferable to include a (meth)acryloyloxy group because it is easy to manufacture, the heat resistance of the dye-containing layer is easily improved, and the adhesion between the dye-containing layer and the substrate is easily adjusted. In this specification, (meth)acryloyl means acryloyl or methacryloyl.
[0139] Examples of polymerizable liquid crystal compounds exhibiting smectic liquid crystal properties include compounds represented by the following formula (Z) (hereinafter sometimes referred to as "polymerizable liquid crystal compound (Z)"). U1z -V 1z -W 1z -(X 1z -Y 1z -) nz -X 2z -W 2z -V 2z -U 2z (Z) [In formula (Z), X 1z and X 2z Each of these independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group, where the hydrogen atoms in the divalent aromatic group or divalent alicyclic hydrocarbon group may be substituted with halogen atoms, C1-C4 alkyl groups, C1-C4 fluoroalkyl groups, C1-C4 alkoxy groups, cyano groups, or nitro groups, and the carbon atoms constituting the divalent aromatic group or divalent alicyclic hydrocarbon group may be substituted with oxygen atoms, sulfur atoms, or nitrogen atoms. However, X 1z and X 2z At least one of these is a optionally substituted 1,4-phenylene group or an optionally substituted cyclohexane-1,4-diyl group. Y 1z It is a single bond or a divalent linking group. nz is 1 to 3, and if nz is 2 or greater, there are multiple X 1z They may be the same or they may be different. 2z is multiple X 1z It may be the same as or different from any or all of the following. Also, if nz is 2 or more, there may be multiple Y 1z These values may be the same or different. From the viewpoint of liquid crystalline properties, nz is preferably 2 or greater. U 1z represents a hydrogen atom or a (meth)acryloyloxy group. U 2z This represents a polymerizable group. W 1z and W 2z These are, independently of each other, single or divalent linking groups. V 1z and V 2zEach of these independently represents an alkanediyl group having 1 to 20 carbon atoms, which may have substituents, and the -CH2- constituting the alkanediyl group may be replaced with -O-, -CO-, -S-, or -NH-.
[0140] In polymerizable liquid crystal compound (Z), X 1z and X 2z These are, independently of each other, preferably a substituted 1,4-phenylene group or a substituted cyclohexane-1,4-diyl group, X 1z and X 2z At least one of these is an optionally substituted 1,4-phenylene group or an optionally substituted cyclohexane-1,4-diyl group, preferably a trans-cyclohexane-1,4-diyl group. Optional substituents on the optionally substituted 1,4-phenylene group or the optionally substituted cyclohexane-1,4-diyl group include C1-C4 alkyl groups such as methyl, ethyl, and butyl groups, cyano groups, and halogen atoms such as chlorine and fluorine atoms. It is preferably unsubstituted.
[0141] Furthermore, polymerizable liquid crystal compound (Z) is defined by formula (Z1): -(X 1z -Y 1z -) n -X 2z - (Z1) [In formula (Z1), X 1z , Y 1z , X 2z And nz have the same meanings as above. The part indicated by ] (hereinafter sometimes referred to as "substructure (Z1)") is preferable to have an asymmetric structure in that it is more likely to exhibit smectic liquid crystal properties. A polymerizable liquid crystal compound (Z) in which the substructure (Z1) is asymmetric is, for example, one in which nz is 1 and one X 1z and X 2z A polymerizable liquid crystal compound (Z) in which the two have different structures is also an example. 1z Compounds in which two X have the same structure1z They have the same structure as each other, and one X 2z These two X 1z Polymerizable liquid crystal compound (Z), which has a different structure from two X 1z W 1z X that binds 1z However, the other X 1z and X 2z It has a different structure, and the other X 1z and X 2z Another example is a polymerizable liquid crystal compound (Z) which has the same structure as the others. Furthermore, nz is 3, and there are three Y 1z Compounds in which the three X's are identical in structure 1z and one X 2z A polymerizable liquid crystal compound (Z) is one in which one of the structures is different from all three others.
[0142] Y 1z -CH2CH2-, -CH2O-, -CH2CH2O-, -COO-, -OCOO-, single bond, -N=N-, -CR az =CR bz -, -C≡C-, -CR az =N- or -CO-NR az - is preferable. az and R bz Each of these independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. 1z It is more preferably -CH2CH2-, -COO-, or a single bond, and multiple Y 1z If X 2z Y that combines with 1z It is more preferable that it be -CH2CH2- or -CH2O-. 1z and X 2z If all have the same structure, then two or more Y have different bonding methods. 1z It is preferable that multiple Ys with different coupling methods exist. 1z When present, an asymmetric structure is formed, which tends to lead to the development of smectic liquid crystal properties.
[0143] U 2z U is the polymerizable group described above.1z This is a hydrogen atom or a polymerizable group. The polymerizable group is preferably a (meth)acryloyloxy group because it is easy to manufacture, the heat resistance of the dye-containing layer is easily improved, and the adhesion between the dye-containing layer and the substrate is easily adjusted. The polymerizable group may be in a polymerized state or an unpolymerized state, but it is preferably in an unpolymerized state.
[0144] V 1z and V 2z Examples of alkanediyl groups represented by include methylene group, ethylene group, propane-1,3-diyl group, butane-1,3-diyl group, butane-1,4-diyl group, pentane-1,5-diyl group, hexane-1,6-diyl group, heptane-1,7-diyl group, octane-1,8-diyl group, decane-1,10-diyl group, tetradecane-1,14-diyl group, and icosane-1,20-diyl group. 1z and V 2z The group is preferably an alkanediyl group having 2 to 12 carbon atoms, and more preferably an alkanediyl group having 6 to 12 carbon atoms.
[0145] The alkanediyl group may optionally have substituents such as cyano groups and halogen atoms, but it is preferable that the alkanediyl group be unsubstituted, and more preferably that it be an unsubstituted linear alkanediyl group.
[0146] W 1z and W 2z These are preferably single bonds, -O-, -S-, -COO-, or -OCOO-, and more preferably single bonds or -O-.
[0147] The polymerizable liquid crystal compound (Z) preferably has an asymmetric molecular structure, and more preferably has a substructure represented by the following formulas (Aa) to (Ai). From the viewpoint of exhibiting higher-order smectic liquid crystal properties, it is more preferable to have a substructure represented by formula (Aa), formula (Ab), or formula (Ac). In formulas (Aa) to (Ai), * represents a bond (single bond).
[0148] [ka]
[0149] Examples of polymerizable liquid crystal compounds (Z) include those represented by formulas (A-1) to (A-25). When polymerizable liquid crystal compound (Z) has a cyclohexane-1,4-diyl group, it is preferable that the cyclohexane-1,4-diyl group is in trans form.
[0150] [ka]
[0151] [ka]
[0152] [ka]
[0153] [ka]
[0154] [ka]
[0155] Among these, at least one selected from the group consisting of compounds represented by formulas (A-2), (A-3), (A-4), (A-5), (A-6), (A-7), (A-8), (A-13), (A-14), (A-15), (A-16), and (A-17) is preferred. The polymerizable liquid crystal compound (Z) may be used alone or in combination of two or more.
[0156] Polymerizable liquid crystal compounds (Z) can be produced by known methods, such as those described in Lub et al., Recl. Trav. Chim. Pays-Bas, 115, 321-328 (1996), or Japanese Patent No. 4719156.
[0157] The polymerizable liquid crystal compound that forms the dye-containing layer is preferably a polymerizable liquid crystal compound having a maximum absorption wavelength between 300 and 400 nm. If the polymerizable liquid crystal composition that forms the dye-containing layer contains a photopolymerization initiator, the polymerization reaction and gelation of the polymerizable liquid crystal compound may proceed during long-term storage. However, if the maximum absorption wavelength of the polymerizable liquid crystal compound is between 300 and 400 nm, even if exposed to ultraviolet light during storage, the generation of reactive species from the photopolymerization initiator and the progression of the polymerization reaction and gelation of the polymerizable liquid crystal compound by these reactive species can be effectively suppressed. Therefore, this is advantageous in terms of the long-term stability of the polymerizable liquid crystal composition and can improve the orientation and uniformity of the film thickness of the resulting dye-containing layer. The maximum absorption wavelength of the polymerizable liquid crystal compound can be measured using an ultraviolet-visible spectrophotometer in a solvent. The solvent is a solvent that can dissolve the polymerizable liquid crystal compound, and examples include chloroform.
[0158] The content of the polymerizable liquid crystal compound in the polymerizable liquid crystal composition that forms the dye-containing layer is, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, more preferably 85 to 98 parts by mass, and even more preferably 90 to 95 parts by mass, per 100 parts by mass of the solid content of the polymerizable liquid crystal composition. Having the polymerizable liquid crystal compound content within the above range is advantageous from the viewpoint of the orientation of the resulting dye-containing layer. In this specification, the solid content of the polymerizable liquid crystal composition refers to all components of the polymerizable liquid crystal composition excluding volatile components such as organic solvents.
[0159] The polymerizable liquid crystal composition used to form the dye-containing layer may further contain additives such as a solvent, photopolymerization initiator, leveling agent, antioxidant, and photosensitizer, in addition to the polymerizable liquid crystal compound and the dichroic dye. Each of these components may be used individually or in combination of two or more.
[0160] Polymerizable liquid crystal compositions for forming a dye-containing layer are usually applied to a substrate or the like in a dissolved state, so it is preferable that they contain a solvent. The solvent is preferably one that can dissolve the polymerizable liquid crystal compound, and is also preferably one that is inert to the polymerization reaction of the polymerizable liquid crystal compound. Examples of solvents include alcohol solvents such as water, methanol, ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether, 1-methoxy-2-propanol, 2-butoxyethanol, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, propylene glycol methyl ether acetate, and ethyl lactate; and acetone, methyl ethyl ketone, and cyclopentanopropyl alcohol. Examples of solvents include ketone solvents such as ethanol, cyclohexanone, 2-heptanone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; alicyclic hydrocarbon solvents such as ethylcyclohexane; aromatic hydrocarbon solvents such as toluene and xylene; nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; chlorine-containing solvents such as chloroform and chlorobenzene; and amide solvents such as dimethylacetamide, dimethylformamide, N-methyl-2-pyrrolidone (NMP), and 1,3-dimethyl-2-imidazolidinone. These solvents can be used individually or in combination of two or more. Among these, alcohol solvents, ester solvents, ketone solvents, chlorine-containing solvents, amide solvents, and aromatic hydrocarbon solvents are preferred.
[0161] The solvent content in the polymerizable liquid crystal composition is preferably 50 to 98 parts by mass, more preferably 70 to 95 parts by mass, per 100 parts by mass of the polymerizable liquid crystal composition. Therefore, the solid content per 100 parts by mass of the polymerizable liquid crystal composition is preferably 2 to 50 parts by mass. When the solid content is 50 parts by mass or less, the viscosity of the polymerizable liquid crystal composition decreases, resulting in a more uniform layer thickness and a tendency for unevenness to occur. The above solid content can be appropriately determined considering the thickness of the dye-containing layer to be manufactured.
[0162] A polymerization initiator is a compound that generates reactive species through the contribution of heat or light, thereby initiating the polymerization reaction of polymerizable liquid crystal compounds and the like. Examples of reactive species include radicals, cations, or anions. Among these, photopolymerization initiators that generate radicals upon light irradiation are preferred from the viewpoint of ease of reaction control.
[0163] Examples of photopolymerization initiators include benzoin compounds, benzophenone compounds, benzyl ketal compounds, α-hydroxyketone compounds, α-aminoketone compounds, oxime compounds, triazine compounds, iodonium salts, and sulfonium salts. Specifically, these include Irgacure (registered trademark) 907, Irgacure 184, Irgacure 651, Irgacure 819, Irgacure 250, Irgacure 369, Irgacure 379, Irgacure 127, Irgacure 2959, Irgacure 754, Irgacure 379EG (all manufactured by BASF Japan Ltd.), Seikaol BZ, Seikaol Z, Seikaol BEE (all manufactured by Seiko Chemical Co., Ltd.), and Kayacure. Examples include ure)BP100 (manufactured by Nippon Kayaku Co., Ltd.), Kayacure UVI-6992 (manufactured by Dow Corporation), Adeka Optomer SP-152, Adeka Optomer SP-170, Adeka Optomer N-1717, Adeka Optomer N-1919, Adeka Arclus NCI-831, Adeka Arclus NCI-930 (all manufactured by ADEKA Corporation), TAZ-A, TAZ-PP (both manufactured by Nippon Siber Hegner Co., Ltd.), and TAZ-104 (manufactured by Sanwa Chemical Co., Ltd.).
[0164] Photopolymerization initiators are preferable to have a maximum absorption wavelength of 300 nm to 400 nm, more preferably 300 nm to 380 nm, as they can fully utilize the energy emitted from the light source and have excellent productivity. Among these, α-acetophenone-based polymerization initiators and oxime-based photopolymerization initiators are preferred.
[0165] Examples of α-acetophenone compounds include 2-methyl-2-morpholino-1-(4-methylsulfanylphenyl)propan-1-one, 2-dimethylamino-1-(4-morpholinophenyl)-2-benzylbutan-1-one, and 2-dimethylamino-1-(4-morpholinophenyl)-2-(4-methylphenylmethyl)butan-1-one, with 2-methyl-2-morpholino-1-(4-methylsulfanylphenyl)propan-1-one and 2-dimethylamino-1-(4-morpholinophenyl)-2-benzylbutan-1-one being more preferred. Commercially available α-acetophenone compounds include Irgacure 369, 379EG, 907 (all manufactured by BASF Japan Ltd.) and Seikol BEE (manufactured by Seiko Chemical Co., Ltd.).
[0166] Oxime-based photopolymerization initiators generate radicals such as phenyl radicals and methyl radicals when irradiated with light. These radicals facilitate the polymerization of polymerizable liquid crystal compounds, and among them, oxime-based photopolymerization initiators that generate methyl radicals are preferred due to their high polymerization reaction initiation efficiency. Furthermore, from the viewpoint of more efficiently advancing the polymerization reaction, it is preferable to use a photopolymerization initiator that can efficiently utilize ultraviolet light with a wavelength of 350 nm or higher. As photopolymerization initiators that can efficiently utilize ultraviolet light with a wavelength of 350 nm or higher, triazine compounds and carbazole compounds containing an oxime structure are preferred, and from the viewpoint of sensitivity, carbazole compounds containing an oxime ester structure are more preferred. Examples of carbazole compounds containing an oxime structure include 1,2-octanedione, 1-[4-(phenylthio)-2-(O-benzoyl oxime)], ethanone, and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-1-(O-acetyl oxime). Commercially available oxime ester-based photopolymerization initiators include Irgacure OXE-01, Irgacure OXE-02, Irgacure OXE-03 (all manufactured by BASF Japan Ltd.), Adeka Optomer N-1919, and Adeka Arclus NCI-831 (both manufactured by ADEKA Corporation).
[0167] The content of the photopolymerization initiator is usually 0.1 to 30 parts by mass, preferably 1 to 20 parts by mass, and more preferably 1 to 15 parts by mass, per 100 parts by mass of the polymerizable liquid crystal compound. Within this range, the reaction of the polymerizable groups proceeds sufficiently, and the orientation of the polymerizable liquid crystal compound is not easily disrupted.
[0168] Leveling agents are additives that adjust the fluidity of polymerizable liquid crystal compositions and make the coating film obtained by applying the composition flatter. Examples include silicone-based, polyacrylate-based, and perfluoroalkyl-based leveling agents. Commercially available leveling agents may be used, specifically DC3PA, SH7PA, DC11PA, SH28PA, SH29PA, SH30PA, ST80PA, ST86PA, SH8400, SH8700, FZ2123 (all manufactured by Toray Dow Corning Co., Ltd.), KP321, KP323, KP324, KP326, KP340, KP341, X22-161A, KF6001 (all manufactured by Shin-Etsu Chemical Co., Ltd.), TSF400, TSF401, TSF410, TSF4300, TSF4440, TSF4445, TSF-4446, TSF4452, TSF4460 (all manufactured by Momentive Performance Materials Co., Ltd.). (Manufactured by Japan LLC), Fluorinert (registered trademark) FC-72, FC-40, FC-43, FC-3283 (all manufactured by Sumitomo 3M Co., Ltd.), Megafac (registered trademark) R-08, R-30, R-90, F-410, F-411, F-443, F-445, F-470, F-477, F-479, F-482, F-483, F-556 (all manufactured by DIC Corporation), F-Top (product name) EF301, EF Examples include 303, EF351, EF352 (all manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.), Surflon® S-381, S-382, S-383, S-393, SC-101, SC-105, KH-40, SA-100 (all manufactured by AGC Seimi Chemical Co., Ltd.), product names E1830 and E5844 (manufactured by Daikin Fine Chemical Laboratories, Inc.), BM-1000, BM-1100, BYK-352, BYK-353, and BYK-361N (all product names: manufactured by BM Chemie). Leveling agents can be used alone or in combination of two or more types.
[0169] The leveling agent content is preferably 0.01 to 5 parts by mass, and more preferably 0.05 to 3 parts by mass, per 100 parts by mass of polymerizable liquid crystal compound. A leveling agent content within the above range is preferable because it facilitates the orientation of the polymerizable liquid crystal compound and tends to result in a smoother dye-containing layer.
[0170] By incorporating antioxidants, the polymerization reaction of polymerizable liquid crystal compounds can be controlled. The antioxidant may be a primary antioxidant selected from phenolic antioxidants, amine antioxidants, quinone antioxidants, or nitroso antioxidants, or a secondary antioxidant selected from phosphorus antioxidants and sulfur antioxidants. To polymerize the polymerizable liquid crystal compound without disrupting its orientation, the antioxidant content is typically 0.01 to 10 parts by mass, preferably 0.1 to 5 parts by mass, and more preferably 0.1 to 3 parts by mass, per 100 parts by mass of the polymerizable liquid crystal compound. Antioxidants can be used alone or in combination of two or more types.
[0171] The photosensitizer can be made highly sensitive by using a photosensitizer. Examples of photosensitizers include xanthones such as xanthones and thioxanthones; substituted anthracenes such as anthracenes and alkyl ethers; phenothiazines; and rubrene. Photosensitizers can be used alone or in combination of two or more. The content of the photosensitizer is usually 0.01 to 10 parts by mass, preferably 0.05 to 5 parts by mass, and more preferably 0.1 to 3 parts by mass, per 100 parts by mass of the polymerizable liquid crystal compound.
[0172] A polymerizable liquid crystal composition can be obtained by stirring a polymerizable liquid crystal compound and the dichroic dye with components other than the polymerizable liquid crystal compound and the dichroic dye, such as a solvent and a photopolymerization initiator, at a predetermined temperature.
[0173] (Method for manufacturing a pigment-containing layer) If the dye-containing layer contains a polymerizable liquid crystal compound, the dye-containing layer is, for example, A process of forming a coating film of a polymerizable liquid crystal composition for forming a dye-containing layer, The process of drying the aforementioned coating film to form a dried coating film, and A process of irradiating a dried coating film with active energy rays to form a pigment-containing layer. It can be manufactured by a method that includes [a specific component].
[0174] The polymerizable liquid crystal composition can be formed by, for example, applying the polymerizable liquid crystal composition for forming a dye-containing layer to a substrate, alignment film, or polarizing layer.
[0175] Examples of substrates include glass substrates and film substrates, but resin film substrates are preferred from the viewpoint of processability. Examples of resins constituting the film substrate include polyolefins such as polyethylene, polypropylene, and norbornene polymers; cyclic olefin resins; polyvinyl alcohol; polyethylene terephthalate; polymethacrylate esters; polyacrylic acid esters; cellulose esters such as triacetylcellulose, diacetylcellulose, and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; polysulfone; polyethersulfone; polyetherketone; polyphenylene sulfide; and plastics such as polyphenylene oxide. Such resins can be formed into film substrates by known means such as solvent casting and melt extrusion. A protective layer formed from acrylic resin, methacrylic resin, epoxy resin, oxetane resin, urethane resin, melamine resin, etc., may be formed on the surface of the film substrate, and a laminate of the film substrate and the protective layer may be used as the substrate. The surface of the film substrate may be subjected to surface treatments such as release treatments like silicone treatment, corona treatment, or plasma treatment, and the film substrate and the layer formed by the surface treatment may be used as the substrate. Examples of protective layers include a hard coat layer (the third hard coat layer described above). Examples of such hard coat layers include the hard coat layer (first hard coat layer) that protects the surface of the dye-containing layer, which will be described later. When a protective layer is provided on the substrate film or when a surface treatment is applied, it is preferable that the alignment film and / or dye-containing layer are laminated on the protective layer side or the surface-treated side.
[0176] Commercially available products may be used as the base material. Examples of commercially available cellulose ester base materials include cellulose ester base materials manufactured by Fuji Photo Film Co., Ltd., such as Fujitac Film; and cellulose ester base materials manufactured by Konica Minolta Opto, Inc., such as "KC8UX2M," "KC8UY," and "KC4UY." Examples of commercially available cyclic olefin resins include cyclic olefin resins manufactured by Ticona GmbH (Germany), such as "Topas®"; cyclic olefin resins manufactured by JSR Corporation, such as "Arton®"; cyclic olefin resins manufactured by Nippon Zeon Co., Ltd., such as "ZEONOR®" and "ZEONEX®"; and cyclic olefin resins manufactured by Mitsui Chemicals, Inc., such as "APPEL®." Commercially available cyclic olefin resin base materials can also be used. Examples of commercially available cyclic olefin resin substrates include cyclic olefin resin substrates manufactured by Sekisui Chemical Co., Ltd., such as "S-Cina®" and "SCA40®"; cyclic olefin resin substrates manufactured by Optes Co., Ltd., such as "Zeonor Film®"; and cyclic olefin resin substrates manufactured by JSR Corporation, such as "Arton Film®".
[0177] From the viewpoint of thinning the optical laminate, ease of peeling the substrate, and handling the substrate, the thickness of the substrate is usually 5 to 300 μm, preferably 10 to 150 μm.
[0178] Methods for applying polymerizable liquid crystal compositions to substrates include known methods such as spin coating, extrusion, gravure coating, die coating, bar coating, and applicator coating, as well as printing methods such as flexographic coating.
[0179] Next, a dried coating film is formed by removing the solvent by drying or other means. Drying methods include natural drying, forced-air drying, heat drying, and reduced-pressure drying. During this process, heating the coating film obtained from the polymerizable liquid crystal composition allows the solvent to be dried and removed from the coating film, and the polymerizable liquid crystal compound can be oriented perpendicular to the coating film plane. The heating temperature of the coating film can be appropriately determined considering the polymerizable liquid crystal compound used and the materials of the substrate on which the coating film is formed, but it is necessary that the temperature be above the liquid crystal phase transition temperature in order to transition the polymerizable liquid crystal compound to a liquid crystal layer state. In order to remove the solvent contained in the polymerizable liquid crystal composition and to align the polymerizable liquid crystal compound perpendicularly, for example, it is possible to heat the coating film to a temperature above the liquid crystal phase transition temperature (smectic phase transition temperature or nematic phase transition temperature) of the polymerizable liquid crystal compound contained in the polymerizable liquid crystal composition.
[0180] The liquid crystal phase transition temperature can be measured using, for example, a polarizing microscope equipped with a temperature control stage, a differential scanning calorimeter (DSC), or a thermogravimetric differential thermal analyzer (TG-DTA). Furthermore, when two or more polymerizable liquid crystal compounds are used in combination, the above phase transition temperature refers to the temperature measured in the same manner as when using a single polymerizable liquid crystal compound, using a mixture of polymerizable liquid crystal compounds obtained by mixing all the polymerizable liquid crystal compounds constituting the polymerizable liquid crystal composition in the same ratio as the composition of the polymerizable liquid crystal composition. It is generally known that the liquid crystal phase transition temperature of a polymerizable liquid crystal compound in the polymerizable liquid crystal composition may be lower than the liquid crystal phase transition temperature of the polymerizable liquid crystal compound as a single compound.
[0181] The heating time can be appropriately determined depending on the heating temperature, the type of polymerizable liquid crystal compound used, the type of solvent, its boiling point, and its amount, but it is usually 15 seconds to 10 minutes, preferably 0.5 to 5 minutes.
[0182] The removal of the solvent from the coating film may be performed simultaneously with heating the polymerizable liquid crystal compound to above its liquid crystal phase transition temperature, or separately, but it is preferable to perform it simultaneously from the viewpoint of improving productivity. Before heating the polymerizable liquid crystal compound to above its liquid crystal phase transition temperature, a pre-drying step may be provided to appropriately remove the solvent in the coating film obtained from the polymerizable liquid crystal composition under conditions in which the polymerizable liquid crystal compound contained in the coating film does not polymerize. Examples of drying methods in such a pre-drying step include natural drying, forced-air drying, heat drying, and reduced-pressure drying, and the drying temperature (heating temperature) in the drying step can be appropriately determined according to the type of polymerizable liquid crystal compound used, the type and boiling point and amount of solvent, etc.
[0183] Next, in the resulting dried coating film, a dye-containing layer is formed by polymerizing the polymerizable liquid crystal compound while maintaining its vertical orientation. Polymerization methods include thermal polymerization and photopolymerization, but photopolymerization is preferred from the viewpoint of easier control of the polymerization reaction. In photopolymerization, the light irradiated onto the dried coating film is appropriately selected according to the type of photopolymerization initiator, the type of polymerizable liquid crystal compound (particularly the type of polymerizable group the polymerizable liquid crystal compound possesses), and its amount. Specific examples include one or more types of light selected from the group consisting of visible light, ultraviolet light, infrared light, X-rays, alpha rays, beta rays, and gamma rays, or active electron beams. Among these, ultraviolet light is preferred because it allows for easy control of the polymerization reaction and because photopolymerization equipment widely used in this field can be used. It is preferable to select the types of polymerizable liquid crystal compounds and photopolymerization initiators contained in the polymerizable liquid crystal composition so that photopolymerization is possible using ultraviolet light. Furthermore, the polymerization temperature can be controlled by irradiating the dried coating film with light while cooling it with appropriate cooling means during polymerization. By employing such cooling methods, polymerization of polymerizable liquid crystal compounds can be carried out at lower temperatures, allowing for the proper formation of a dye-containing layer even when using a substrate with relatively low heat resistance. Furthermore, it is possible to accelerate the polymerization reaction by increasing the polymerization temperature within a range that does not cause problems due to heat during light irradiation (such as deformation of the substrate due to heat). Patterned dye-containing layers can also be obtained by performing masking or development during photopolymerization.
[0184] Examples of light sources for active energy rays include low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, xenon lamps, halogen lamps, carbon arc lamps, tungsten lamps, gallium lamps, excimer lasers, LED light sources emitting in the wavelength range of 380-440 nm, chemical lamps, black light lamps, microwave-excited mercury lamps, and metal halide lamps.
[0185] The UV irradiation intensity is typically 10-3,000 mW / cm². 2 The ultraviolet irradiation intensity is preferably in the wavelength range effective for activating the photopolymerization initiator. The irradiation time is usually 0.1 seconds to 10 minutes, preferably 0.1 seconds to 5 minutes, more preferably 0.1 seconds to 3 minutes, and even more preferably 0.1 seconds to 1 minute. When irradiation is performed once or multiple times at such ultraviolet irradiation intensity, the accumulated light amount is 10 to 3,000 mJ / cm². 2 Preferably 50 to 2,000 mJ / cm² 2 More preferably 100-1,000 mJ / cm² 2 That is the case.
[0186] The coating film of the polymerizable liquid crystal composition may be formed on an alignment film. The alignment film has an alignment restricting force that causes the polymerizable liquid crystal compound to be liquid crystal oriented in a desired direction. Alignment films include horizontal alignment films that have an alignment restricting force that aligns the polymerizable liquid crystal compound horizontally, and vertical alignment films that have an alignment restricting force that aligns it vertically, but the alignment film used when forming a dye-containing layer is a vertical alignment film. The alignment restricting force can be arbitrarily adjusted depending on the type of alignment film, surface condition, rubbing conditions, etc., and if the alignment film is formed from a photo-oriented polymer, it can be arbitrarily adjusted depending on the polarization irradiation conditions, etc.
[0187] The alignment film is preferably solvent-resistant, meaning it will not dissolve when a polymerizable liquid crystal composition is applied, and also heat-resistant for solvent removal and for heat treatment to align the polymerizable liquid crystal compound described later. Examples of alignment films include alignment films containing an aligning polymer, photo-alignment films, groove-alignment films having a surface pattern of irregularities or multiple grooves, and stretched films stretched in the orientation direction. Photo-alignment films are preferred from the viewpoint of accuracy of the orientation angle and quality.
[0188] Examples of oriented polymers include polyamides and gelatins having amide bonds in their molecules, polyimides having imide bonds in their molecules and their hydrolysates such as polyamic acid, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinylpyrrolidone, polyacrylic acid, and polyacrylic acid esters. Among these, polyvinyl alcohol is preferred. The oriented polymers can be used alone or in combination of two or more.
[0189] Orientation films containing oriented polymers are typically obtained by coating a substrate with a composition in which the oriented polymer is dissolved in a solvent (hereinafter sometimes referred to as "oriented polymer composition"), removing the solvent, or by coating a substrate with an oriented polymer composition, removing the solvent, and rubbing (rubbing method). Examples of solvents include those previously exemplified as solvents that can be used in polymerizable liquid crystal compositions.
[0190] The concentration of the oriented polymer in the oriented polymer composition should be within a range in which the oriented polymer material can be completely dissolved in the solvent, but it is preferably 0.1 to 20% in terms of solid content relative to the solution, and more preferably about 0.1 to 10%.
[0191] As the oriented polymer composition, commercially available oriented film materials may be used as is. Examples of commercially available oriented film materials include SunEver (registered trademark, manufactured by Nissan Chemical Industries, Ltd.) and Optomer (registered trademark, manufactured by JSR Corporation).
[0192] Methods for applying the oriented polymer composition to a substrate include those similar to those exemplified for applying the polymerizable liquid crystal composition to a substrate.
[0193] Methods for removing solvents contained in oriented polymer compositions include natural drying, forced-air drying, heat drying, and reduced-pressure drying.
[0194] One method for applying orientation-regulating force using the rubbing method involves applying an orientation-regulating polymer composition to a substrate and annealing it to a rotating rubbing roll around which a rubbing cloth is wrapped, thereby bringing the film of the orientation-regulating polymer formed on the substrate surface into contact with the roll. By masking during the rubbing process, it is also possible to form multiple regions (patterns) with different orientation directions on the orientation film.
[0195] Photoalignment films are typically obtained by coating a substrate with a composition containing a polymer or monomer having a photoreactive group and a solvent (hereinafter sometimes referred to as a "photoalignment film forming composition"), removing the solvent, and then irradiating it with polarized light (preferably polarized UV). Photoalignment films are also advantageous in that the direction of the alignment restricting force can be arbitrarily controlled by selecting the polarization direction of the polarized light used for irradiation.
[0196] A photoreactive group is a group that generates liquid crystal alignment ability upon light irradiation. Specifically, this includes groups involved in photoreactions that are the origin of liquid crystal alignment ability, such as molecular orientation induction or isomerization reactions, dimerization reactions, photocrosslinking reactions, or photodegradation reactions, which are induced by light irradiation. Among these, groups involved in dimerization reactions or photocrosslinking reactions are preferred because they exhibit excellent orientation properties. As photoreactive groups, groups having unsaturated bonds, especially double bonds, are preferred, and groups having at least one selected from the group consisting of carbon-carbon double bonds (C=C bonds), carbon-nitrogen double bonds (C=N bonds), nitrogen-nitrogen double bonds (N=N bonds), and carbon-oxygen double bonds (C=O bonds) are particularly preferred.
[0197] Examples of photoreactive groups having a C=C bond include vinyl groups, polyene groups, stilbene groups, stilbazole groups, stilbazolium groups, chalcone groups, and cinnamoyl groups. Examples of photoreactive groups having a C=N bond include groups having structures such as aromatic Schiff bases and aromatic hydrazones. Examples of photoreactive groups having an N=N bond include azobenzene groups, azonaphthalene groups, aromatic heterocyclic azo groups, bisazo groups, formazan groups, and groups having an azoxybenzene structure. Examples of photoreactive groups having a C=O bond include benzophenone groups, coumarin groups, anthraquinone groups, and maleimide groups. These groups may have substituents such as alkyl groups, alkoxy groups, allyl groups, allyloxy groups, cyano groups, alkoxycarbonyl groups, hydroxyl groups, sulfonic acid groups, and halogenated alkyl groups.
[0198] Among these, photoreactive groups involved in the photodimerization reaction are preferred, and cinnamoyl groups and chalcone groups are preferred because they require a relatively small amount of polarized irradiation for photo-orientation, and it is easy to obtain a photo-orientation film with excellent thermal stability and chronological stability. As for polymers having photoreactive groups, those having cinnamoyl groups such that the terminal portion of the polymer side chain has a cinnamic acid structure are particularly preferred.
[0199] A photo-alignment film-forming composition can be applied to a substrate to form a photo-alignment-inducing layer on the substrate. Examples of solvents included in the composition are those previously exemplified as solvents usable in polymerizable liquid crystal compositions, and can be appropriately selected depending on the solubility of the polymer or monomer having a photoreactive group.
[0200] The content of photo-alignment film-forming polymers or monomers having photoreactive groups in the photo-alignment film-forming composition can be appropriately adjusted depending on the type of polymer or monomer and the desired thickness of the photo-alignment film, but it is preferably at least 0.2% by mass, and more preferably in the range of 0.3 to 10% by mass, relative to the mass of the photo-alignment film-forming composition. The photo-alignment film-forming composition may also contain polymer materials such as polyvinyl alcohol or polyimide, or photosensitizers, as long as the properties of the photo-alignment film are not significantly impaired.
[0201] Methods for applying the photo-alignment film-forming composition to a substrate include those similar to those for applying an oriented polymer composition to a substrate. Methods for removing the solvent from the applied photo-alignment film-forming composition include, for example, natural drying, forced-air drying, heat drying, and reduced-pressure drying.
[0202] To irradiate with polarized light, the polarized UV light may be directly irradiated onto a photo-alignment film-forming composition coated on a substrate from which the solvent has been removed, or polarized light may be irradiated from the substrate side and transmitted through to the surface. Furthermore, it is particularly preferable that the polarized light is substantially parallel light. The wavelength of the polarized light to be irradiated should be in the wavelength range in which the photoreactive groups of the polymer or monomer having photoreactive groups can absorb light energy. Specifically, UV (ultraviolet) light in the wavelength range of 250 to 400 nm is particularly preferred. Examples of light sources used for this polarized light irradiation include xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, and ultraviolet light lasers such as KrF and ArF, with high-pressure mercury lamps, ultra-high-pressure mercury lamps and metal halide lamps being more preferred. Among these, high-pressure mercury lamps, ultra-high-pressure mercury lamps and metal halide lamps are preferred because they have a high emission intensity of ultraviolet light at a wavelength of 313 nm. Polarized UV light can be irradiated by passing light from a light source through a suitable polarizer. Such polarizers can include polarizing filters, polarizing prisms such as Grant-Thomson and Grant-Taylor, and wire grid type polarizers.
[0203] By masking during rubbing or polarized irradiation, it is possible to form multiple regions (patterns) with different orientations of the liquid crystal compound.
[0204] A groove-aligned film is a film having an uneven pattern or multiple grooves on its surface. When a polymerizable liquid crystal compound is applied to a film having multiple linear grooves arranged at equal intervals, the liquid crystal molecules align in the direction along the grooves.
[0205] Methods for obtaining a groove-aligned film include a method of forming an uneven pattern by exposing a photosensitive polyimide film surface through an exposure mask having pattern-shaped slits, followed by development and rinsing; a method of forming a layer of UV-curable resin before curing on a plate-shaped master disc having grooves on its surface, transferring the formed resin layer to a substrate, and then curing it; and a method of forming an uneven surface by pressing a roll-shaped master disc having multiple grooves against an uncured UV-curable resin film formed on a substrate, and then curing it.
[0206] In addition to the orientation-regulating polymers mentioned above, materials that exhibit orientation-regulating force to orient polymerizable liquid crystal compounds perpendicular to the coating film plane may also be used as materials such as fluorine-based polymers such as perfluoroalkyls, silane compounds, and polysiloxane compounds obtained by their condensation reactions.
[0207] When using a silane compound as the material for forming the orientation film, a compound containing Si and C elements as constituent elements is preferred from the viewpoint of easily lowering surface tension and easily improving adhesion to the adjacent layer to the orientation film, and a silane compound can be suitably used. As the silane compound, nonionic silane compounds described later, or silane-containing ionic compounds as exemplified by the ionic compounds described later can be used, and the vertical orientation restricting force can be increased by using these silane compounds. These silane compounds may be used individually, in combination of two or more, or mixed with other materials. When the silane compound is a nonionic silane compound, a silane compound having an alkyl group at the molecular end is preferred from the viewpoint of easily increasing the vertical orientation restricting force, and a silane compound having an alkyl group with 3 to 30 carbon atoms is more preferred.
[0208] The thickness of the orientation film (or photo-alignment film containing an oriented polymer) is typically in the range of 10 to 10,000 nm, preferably in the range of 10 to 1,000 nm, more preferably 10 to 500 nm or less, even more preferably 10 to 300 nm, and particularly preferably in the range of 50 to 250 nm.
[0209] A polymerizable liquid crystal composition coating may be formed directly on the substrate without using an alignment film. When a polymerizable liquid crystal composition coating is formed directly on the substrate, the process of forming an alignment film is not required, which is advantageous in terms of production efficiency and production cost. In this case, the polymerizable liquid crystal composition for forming the dye-containing layer usually contains an alignment promoter. An alignment promoter is a material that promotes the liquid crystal alignment of the polymerizable liquid crystal compound in a desired direction.
[0210] Orientation promoters that promote the vertical orientation of polymerizable liquid crystal compounds include ionic compounds and nonionic silane compounds composed of nonmetallic atoms. It is preferable that the polymerizable liquid crystal composition forming the dye-containing layer contains at least one of the ionic compounds and nonionic silane compounds composed of nonmetallic atoms, and more preferably contains both the ionic compounds and nonionic silane compounds.
[0211] When the polymerizable liquid crystal composition that forms the dye-containing layer contains an ionic compound made of nonmetallic atoms, a vertical orientation restricting force is exerted on the polymerizable liquid crystal compound in the dried coating film formed on the substrate using the polymerizable liquid crystal composition for forming the dye-containing layer due to electrostatic interactions. As a result, the polymerizable liquid crystal compound tends to orient perpendicularly to the substrate surface within the dried coating film. This allows the dye-containing layer to be formed while maintaining the vertical orientation of the polymerizable liquid crystal compound.
[0212] Examples of ionic compounds consisting of nonmetallic atoms include onium salts (more specifically, quaternary ammonium salts, tertiary sulfonium salts, and quaternary phosphonium salts, etc., in which the nitrogen atom has a positive charge). Of these onium salts, quaternary onium salts are preferred from the viewpoint of further improving the vertical orientation of polymerizable liquid crystal compounds, and quaternary phosphonium salts or quaternary ammonium salts are more preferred from the viewpoint of improving availability and mass production. Onium salts may have two or more quaternary onium salt moieties in the molecule, and may be oligomers or polymers.
[0213] The molecular weight of the ionic compound is preferably between 100 and 10,000. When the molecular weight is within this range, it is easier to improve the vertical orientation of the polymerizable liquid crystal compound while ensuring the coatability of the polymerizable liquid crystal composition. More preferably, the molecular weight of the ionic compound is 5,000 or less, and even more preferably 3,000 or less.
[0214] Examples of cation components in ionic compounds include inorganic cations and organic cations. Among these, organic cations are preferred because they are less likely to cause orientation defects in polymerizable liquid crystal compounds. Examples of organic cations include imidazolium cations, pyridinium cations, ammonium cations, sulfonium cations, and phosphonium cations.
[0215] Ionic compounds generally have counter anions. Examples of anion components that act as counterions to the cationic components include inorganic and organic anions. Among these, organic anions are preferred because they are less likely to cause orientation defects in polymerizable liquid crystal compounds. It should be noted that there is not necessarily a one-to-one correspondence between cations and anions.
[0216] Examples of anionic components include the following: Chloride anion [Cl - ), Bromide Anion [Br - ), Iodion [I - ), Tetrachloroaluminate anion [AlCl4] - ), Heptachlorodialuminate anion [Al2Cl7] - ), Tetrafluoroborate anion [BF4] - ), Hexafluorophosphate anion [PF6] - ), Perchlorate anion [ClO4] - ), Nitrate anion [NO3]- ), Acetate anion [CH3COO - ), Trifluoroacetate anion [CF3COO - ), Fluorosulfonate anion [FSO3 - ), Methanesulfonate anion [CH3SO3] - ), Trifluoromethanesulfonate anion [CF3SO3] - ), p-toluenesulfonate anion [p-CH3C6H4SO3] - ), Bis(fluorosulfonyl)imido anion [(FSO2)2N] - ), Bis(trifluoromethanesulfonyl)imido anion [(CF3SO2)2N] - ), Tris(trifluoromethanesulfonyl)methanide anion [(CF3SO2)3C - ), Hexafluoroarsenate anion [AsF6] - ), Hexafluoroantimonate anion [SbF6] - ), Hexafluoroniobate anion [NbF6] - ), Hexafluorotantalate anion [TaF6] - ), Dimethylphosphinate anion [(CH3)2POO - ), (Poly)hydrofluorofluoride anion [F(HF)] n - (For example, n represents an integer between 1 and 3.) Dicyanamide anion [(CN)2N - ), Thiocyanine anion [SCN - ), Perfluorobutanesulfonate anion [C4F9SO3 - ), Bis(pentafluoroethanesulfonyl)imide anion [(C2F5SO2)2N - ), Perfluorobutanoate anion [C3F7COO - ), and, (Trifluoromethanesulfonyl)(Trifluoromethanecarbonyl)imido anion [(CF3SO2)(CF3CO)N - ]
[0217] Specific examples of ionic compounds can be appropriately selected from the above combinations of cationic and anionic components. Examples of compounds with specific combinations of cationic and anionic components include the following:
[0218] (Pyridinium salt) N-hexylpyridinium hexafluorophosphate, N-octylpyridinium hexafluorophosphate, N-methyl-4-hexylpyridinium hexafluorophosphate, N-butyl-4-methylpyridinium hexafluorophosphate, N-octyl-4-methylpyridinium hexafluorophosphate, N-hexylpyridinium bis(fluorosulfonyl)imide, N-octylpyridinium bis(fluorosulfonyl)imide, N-methyl-4-hexylpyridinium bis(fluorosulfonyl)imide, N-butyl-4-methylpyridinium bis(fluorosulfonyl)imide, N-octyl-4-methylpyridinium bis(fluorosulfonyl)imide, N-Hexylpyridinium bis(trifluoromethanesulfonyl)imide N-octylpyridinium bis(trifluoromethanesulfonyl)imide, N-methyl-4-hexylpyridinium bis(trifluoromethanesulfonyl)imide N-butyl-4-methylpyridinium bis(trifluoromethanesulfonyl)imide N-octyl-4-methylpyridinium bis(trifluoromethanesulfonyl)imide, N-hexylpyridinium p-toluenesulfonate, N-octylpyridinium p-toluenesulfonate, N-methyl-4-hexylpyridinium p-toluenesulfonate, N-butyl-4-methylpyridinium p-toluenesulfonate, and N-octyl-4-methylpyridinium p-toluenesulfonate.
[0219] (Imidazorium salt) 1-Ethyl-3-methylimidazolium hexafluorophosphate, 1-Ethyl-3-methylimidazolium bis(fluorosulfonyl)imide, 1-Ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide 1-Ethyl-3-methylimidazolium p-toluenesulfonate, 1-Butyl-3-methylimidazolium methanesulfonate, etc.
[0220] (Pyrrolidinium salt) N-butyl-N-methylpyrrolidinium hexafluorophosphate, N-butyl-N-methylpyrrolidinium bis(fluorosulfonyl)imide N-butyl-N-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide N-butyl-N-methylpyrrolidinium p-toluenesulfonate, etc.
[0221] (Ammonium salt) Tetrabutylammonium hexafluorophosphate, Tetrabutylammonium bis(fluorosulfonyl)imide, Tetrahexylammonium bis(fluorosulfonyl)imide, Trioctylmethylammonium bis(fluorosulfonyl)imide, (2-hydroxyethyl)trimethylammonium bis(fluorosulfonyl)imide Tetrabutylammonium bis(trifluoromethanesulfonyl)imide, Tetrahexylammonium bis(trifluoromethanesulfonyl)imide, Trioctylmethylammonium bis(trifluoromethanesulfonyl)imide, (2-hydroxyethyl)trimethylammonium bis(trifluoromethanesulfonyl)imide Tetrabutylammonium p-toluenesulfonate, Tetrahexylammonium p-toluenesulfonate, Trioctylmethylammonium p-toluenesulfonate, (2-hydroxyethyl)trimethylammonium p-toluenesulfonate, (2-hydroxyethyl)trimethylammonium dimethylphosphine, 1-(3-trimethoxysilylpropyl)-1,1,1-tributylammonium bis(trifluoromethanesulfonyl)imide 1-(3-trimethoxysilylpropyl)-1,1,1-trimethylammonium bis(trifluoromethanesulfonyl)imide, 1-(3-trimethoxysilylbutyl)-1,1,1-tributylammonium bis(trifluoromethanesulfonyl)imide 1-(3-trimethoxysilylbutyl)-1,1,1-trimethylammonium bis(trifluoromethanesulfonyl)imide N-{(3-triethoxysilylpropyl)carbamoyloxyethyl)}-N,N,N-trimethylammonium bis(trifluoromethanesulfonyl)imide, and, N-[2-{3-(3-trimethoxysilylpropylamino)-1-oxopropoxy}ethyl]-N,N,N-trimethylammonium bis(trifluoromethanesulfonyl)imide.
[0222] (Phosphonium salt) Tributyl(2-methoxyethyl)phosphonium bis(trifluoromethanesulfonyl)imide, Tributylmethylphosphonium bis(trifluoromethanesulfonyl)imide, 1,1,1-trimethyl-1-[(trimethoxysilyl)methyl]phosphonium bis(trifluoromethanesulfonyl)imide 1,1,1-Trimethyl-1-[2-(trimethoxysilyl)ethyl]phosphonium bis(trifluoromethanesulfonyl)imide 1,1,1-Trimethyl-1-[3-(trimethoxysilyl)propyl]phosphonium bis(trifluoromethanesulfonyl)imide 1,1,1-Trimethyl-1-[4-(trimethoxysilyl)butyl]phosphonium bis(trifluoromethanesulfonyl)imide 1,1,1-Tributyl-1-[(trimethoxysilyl)methyl]phosphonium bis(trifluoromethanesulfonyl)imide 1,1,1-Tributyl-1-[2-(trimethoxysilyl)ethyl]phosphonium bis(trifluoromethanesulfonyl)imide, and 1,1,1-Tributyl-1-[3-(trimethoxysilyl)propyl]phosphoniubis(trifluoromethanesulfonyl)imide.
[0223] These ionic compounds may be used individually or in combination of two or more.
[0224] From the viewpoint of further improving the vertical orientation of polymerizable liquid crystal compounds, it is preferable that the ionic compound has Si and / or F elements in the molecular structure of the cation moiety. When the ionic compound has Si and / or F elements in the molecular structure of the cation moiety, it becomes easier to segregate the ionic compound on the surface of the dye-containing layer. Among these, the following ionic compounds (Ii) to (I-iii) are preferred as ionic compounds in which all constituent elements are nonmetallic elements.
[0225] (Ionic compounds (Ii)) [ka]
[0226] (Ionic compounds (I-II)) [ka]
[0227] (Ionic compounds (I-III)) [ka]
[0228] One known method for improving the vertical orientation of polymerizable liquid crystal compounds is to treat the substrate surface with a surfactant having an alkyl group with a relatively long chain length (see, for example, Chapter 2, Orientation and Properties of Liquid Crystals, "Liquid Crystal Handbook" (published by Maruzen Co., Ltd.)). This method of improving the vertical orientation of liquid crystal compounds with surfactants can also be applied to ionic compounds. That is, by treating the substrate surface with an ionic compound having an alkyl group with a relatively long chain length, the vertical orientation of polymerizable liquid crystal compounds can be effectively improved.
[0229] Specifically, it is preferable that the ionic compound satisfies the relationship shown in formula (8) below. 5 <M<16 (8) [In equation (8), M is expressed by the following equation (9). M = (The number of covalent bonds from the positively charged atom to the end of the molecular chain of the substituent that has the most covalent bonds from the positively charged atom to the end of the molecular chain among substituents directly bonded to a positively charged atom) ÷ (Number of positively charged atoms) (9)]
[0230] By satisfying the relationship in formula (8) above, the ionic compound can effectively improve the vertical orientation of the polymerizable liquid crystal compound.
[0231] If an ionic compound molecule contains two or more positively charged atoms, for substituents containing two or more positively charged atoms, the number of covalent bonds from the positively charged atom considered as the starting point to the nearest other positively charged atom shall be used as the "number of covalent bonds from the positively charged atom to the end of the molecular chain" as defined above for M. Furthermore, if the ionic compound is an oligomer or polymer with two or more repeating units, the constituent units shall be considered as one molecule, and M shall be calculated accordingly. If a positively charged atom is incorporated into a ring structure, the number of covalent bonds from the positively charged atom to the positively charged atom via the ring structure, or the number of covalent bonds to the end of the substituent bonded to the ring structure, whichever is greater, shall be used as the "number of covalent bonds from the positively charged atom to the end of the molecular chain" as defined above for M.
[0232] When the polymerizable liquid crystal composition forming the dye-containing layer contains an ionic compound, its content is usually preferably 0.01 to 5% by mass, more preferably 0.05 to 4% by mass, and even more preferably 0.1 to 3% by mass, relative to the solid content of the polymerizable liquid crystal composition. When the content of the ionic compound is within the above range, the vertical orientation of the polymerizable liquid crystal compound can be effectively promoted while maintaining the good coatability of the polymerizable liquid crystal composition.
[0233] When the polymerizable liquid crystal composition forming the dye-containing layer contains a nonionic silane compound, the nonionic silane compound reduces the surface tension of the polymerizable liquid crystal composition. In the dried coating film formed on the substrate from the polymerizable liquid crystal composition for forming the dye-containing layer, the nonionic silane compound is present on the side of the dried coating film opposite to the substrate, increasing the vertical orientation restricting force for the polymerizable liquid crystal compound. This causes the polymerizable liquid crystal compound to tend to orient perpendicularly to the substrate surface within the dried coating film. As a result, the dye-containing layer can be formed while maintaining the vertical orientation of the polymerizable liquid crystal compound.
[0234] Nonionic silane compounds are compounds that are nonionic and contain the element Si. Examples of nonionic silane compounds include silicon polymers such as polysilanes, silicone resins such as silicone oils and silicone resins, and organic inorganic silane compounds such as silicone oligomers, silethsiloxanes and alkoxysilanes (more specifically, silane coupling agents, etc.), and silane-containing compounds exemplified as leveling agents.
[0235] The nonionic silane compound may be of the silicone monomer type or the silicone oligomer (polymer) type. When the silicone oligomer is expressed in the form of a (monomer)-(monomer) copolymer, it may include mercaptopropyl group-containing copolymers such as 3-mercaptopropyltrimethoxysilane-tetramethoxysilane copolymer, 3-mercaptopropyltrimethoxysilane-tetraethoxysilane copolymer, 3-mercaptopropyltriethoxysilane-tetramethoxysilane copolymer, and 3-mercaptopropyltriethoxysilane-tetraethoxysilane copolymer; mercaptomethyl group-containing copolymers such as mercaptomethyltrimethoxysilane-tetramethoxysilane copolymer, mercaptomethyltriethoxysilane-tetramethoxysilane copolymer, and mercaptomethyltriethoxysilane-tetraethoxysilane copolymer; and 3-meth Methacryloyloxypropyl group-containing copolymers such as cryoyloxypropyltrimethoxysilane-tetramethoxysilane copolymer, 3-methacryloyloxypropyltrimethoxysilane-tetraethoxysilane copolymer, 3-methacryloyloxypropyltriethoxysilane-tetramethoxysilane copolymer, 3-methacryloyloxypropyltriethoxysilane-tetraethoxysilane copolymer, 3-methacryloyloxypropylmethyldimethoxysilane-tetramethoxysilane copolymer, 3-methacryloyloxypropylmethyldimethoxysilane-tetraethoxysilane copolymer, 3-methacryloyloxypropylmethyldiethoxysilane-tetramethoxysilane copolymer, and 3-methacryloyloxypropylmethyldiethoxysilane-tetraethoxysilane copolymer;3-Acryloyloxypropyltrimethoxysilane-tetramethoxysilane copolymer, 3-Acryloyloxypropyltrimethoxysilane-tetraethoxysilane copolymer, 3-Acryloyloxypropyltriethoxysilane-tetramethoxysilane copolymer, 3-Acryloyloxypropyltriethoxysilane-tetraethoxysilane copolymer, 3-Acryloyloxypropylmethyldimethoxysilane-tetramethoxysilane copolymer, 3-Acryloyloxypropylmethyldimethoxysilane-tetraethoxysilane copolymer, 3-Acryloyloxypropylmethyldiethoxysilane-tetramethoxysilane copolymer and 3-Acryloyloxypropyl Copolymers containing acryloyloxypropyl groups, such as tyldiethoxysilane-tetraethoxysilane copolymer; copolymers containing vinyl groups, such as vinyltrimethoxysilane-tetramethoxysilane copolymer, vinyltrimethoxysilane-tetraethoxysilane copolymer, vinyltriethoxysilane-tetramethoxysilane copolymer, vinyltriethoxysilane-tetraethoxysilane copolymer, vinylmethyldimethoxysilane-tetramethoxysilane copolymer, vinylmethyldimethoxysilane-tetraethoxysilane copolymer, vinylmethyldiethoxysilane-tetramethoxysilane copolymer, and vinylmethyldiethoxysilane-tetraethoxysilane copolymer;Examples include amino group-containing copolymers such as 3-aminopropyltrimethoxysilane-tetramethoxysilane copolymer, 3-aminopropyltrimethoxysilane-tetraethoxysilane copolymer, 3-aminopropyltriethoxysilane-tetramethoxysilane copolymer, 3-aminopropyltriethoxysilane-tetraethoxysilane copolymer, 3-aminopropylmethyldimethoxysilane-tetramethoxysilane copolymer, 3-aminopropylmethyldimethoxysilane-tetraethoxysilane copolymer, 3-aminopropylmethyldiethoxysilane-tetramethoxysilane copolymer, and 3-aminopropylmethyldiethoxysilane-tetraethoxysilane copolymer. These nonionic silane compounds may be used individually or in combination of two or more. Among these, silane coupling agents are preferred from the viewpoint of further improving adhesion with adjacent layers.
[0236] A silane coupling agent is a compound containing an element Si having at least one functional group selected from the group consisting of vinyl, epoxy, styryl, methacrylic, acrylic, amino, isocyanurate, ureido, mercapto, isocyanate, carboxy, and hydroxyl groups at its terminal, and at least one alkoxysilyl or silanol group. By appropriately selecting these functional groups, it is possible to impart unique effects such as improved mechanical strength of the dye-containing layer, surface modification of the dye-containing layer, and improved adhesion between the dye-containing layer and adjacent layers (e.g., substrates). From the viewpoint of adhesion, it is preferable that the silane coupling agent has an alkoxysilyl group and another different reactive group (e.g., the above functional group). Furthermore, it is preferable that the silane coupling agent has an alkoxysilyl group and a polar group. When a silane coupling agent has at least one alkoxysilyl group and at least one polar group in its molecule, the vertical orientation of the polymerizable liquid crystal compound tends to improve more easily, and a significant vertical orientation promoting effect is likely to be obtained. Examples of polar groups include epoxy groups, amino groups, isocyanurate groups, mercapto groups, carboxyl groups, and hydroxyl groups. The polar groups may have substituents or protecting groups as appropriate to control the reactivity of the silane coupling agent.
[0237] Examples of silane coupling agents include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(2-methoxyethoxy)silane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, 3-glycidoxypropyltrimethoxysilane, and 3-glycidoxypropyl Examples include tyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-chloropropylmethyldimethoxysilane, 3-chloropropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropyldimethoxymethylsilane, and 3-glycidoxypropylethoxydimethylsilane.
[0238] Examples of commercially available silane coupling agents include KP321, KP323, KP324, KP326, KP340, KP341, X22-161A, KF6001, KBM-1003, KBE-1003, KBM-303, KBM-402, KBM-403, KBE-402, KBE-403, KBM-1403, KBM-502, KBM-503, KBE- Examples of silane coupling agents manufactured by Shin-Etsu Chemical Co., Ltd. include 502, KBE-503, KBM-5103, KBM-602, KBM-603, KBM-903, KBE-903, KBE-9103, KBM-573, KBM-575, KBM-9659, KBE-585, KBM-802, KBM-803, KBE-846, and KBE-9007.
[0239] When the polymerizable liquid crystal composition forming the dye-containing layer contains a nonionic silane compound, its content is usually preferably 0.01% to 5% by mass, more preferably 0.05% to 4% by mass, and even more preferably 0.1% to 3% by mass, relative to the solid content of the polymerizable liquid crystal composition. When the content of the nonionic silane compound is within the above range, the vertical orientation of the polymerizable liquid crystal compound can be effectively promoted while maintaining the good coatability of the polymerizable liquid crystal composition.
[0240] When the polymerizable liquid crystal composition forming the dye-containing layer contains both an ionic compound and a nonionic silane compound, the vertical orientation of the polymerizable liquid crystal compound is more easily promoted in the dried coating film formed from the polymerizable liquid crystal composition on the substrate due to electrostatic interactions originating from the ionic compound and the surface tension reduction effect from the nonionic silane compound. As a result, the dye-containing layer can be formed while maintaining a state in which the polymerizable liquid crystal compound is more precisely vertically oriented.
[0241] (Stretched film that constitutes the phase difference layer) Conventional stretched films can be used as the stretched film constituting the phase difference layer, and films in which an in-plane phase difference is imparted by uniaxial or biaxial stretching of a resin film can be used. As resin films, cellulose-based films such as triacetylcellulose and diacetylcellulose, polyester-based films such as polyethylene terephthalate, polyethylene isophthalate and polybutylene terephthalate, acrylic resin-based films such as polymethyl (meth)acrylate and polyethyl (meth)acrylate, polycarbonate-based films, polyethersulfone-based films, polysulfone-based films, polyimide-based films, polyolefin-based films, polynorbornene-based films, etc. can be used, but are not limited to these.
[0242] (Horizontal alignment liquid crystal layer) Conventional polymerizable liquid crystal compounds can be used as polymerizable liquid crystal compounds to form the horizontally aligned liquid crystal layer constituting the phase difference layer. In particular, polymerizable liquid crystal compounds exhibiting so-called inverse wavelength dispersion are preferred, and as such polymerizable liquid crystal compounds, for example, the compound represented by formula (X) above can be suitably used. Polymerizable liquid crystal compounds can be used alone or in combination of two or more.
[0243] The content of the polymerizable liquid crystal compound in the polymerizable liquid crystal composition used to form the horizontally aligned liquid crystal layer is, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, more preferably 85 to 98 parts by mass, and even more preferably 90 to 95 parts by mass, per 100 parts by mass of the solid content of the polymerizable liquid crystal composition. A content of the polymerizable liquid crystal compound within the above range is advantageous from the viewpoint of the orientation of the resulting horizontally aligned liquid crystal layer.
[0244] The polymerizable liquid crystal composition used to form the horizontally aligned liquid crystal layer may further contain additives such as a solvent, a photopolymerization initiator, a leveling agent, an antioxidant, and a photosensitizer, in addition to the polymerizable liquid crystal compound. Examples of these components include those previously exemplified as components that can be used in the dye-containing layer, and each may be used individually or in combination of two or more.
[0245] A polymerizable liquid crystal composition used for forming a horizontally aligned liquid crystal layer can be obtained by stirring a polymerizable liquid crystal compound with components other than the polymerizable liquid crystal compound, such as a solvent or a photopolymerization initiator, at a predetermined temperature.
[0246] A horizontally aligned liquid crystal layer is, for example, A process of obtaining a coating film by applying a polymerizable liquid crystal compound for forming a horizontally aligned liquid crystal layer onto a substrate or alignment film, The process of drying the above coating to form a dried coating, and A process of irradiating a dried coating film with active energy rays to form a horizontally aligned liquid crystal layer. It can be manufactured by a method that includes [a specific component].
[0247] The polymerizable liquid crystal composition can be formed by, for example, applying the polymerizable liquid crystal composition for forming a horizontally aligned liquid crystal layer onto a substrate or an alignment film. The substrates that can be used here are those previously exemplified as substrates that can be used for manufacturing a dye-containing layer.
[0248] The alignment film can be a horizontal alignment film having a horizontal alignment restricting force that aligns polymerizable liquid crystal compounds horizontally with respect to the coating film plane. The alignment restricting force can be arbitrarily adjusted depending on the type of alignment film, surface condition, rubbing conditions, etc., and if it is formed from a photo-aligning polymer, it can be arbitrarily adjusted depending on the polarized irradiation conditions, etc. Examples of such materials include the aligning polymer described as an alignment film that can be used in the production of a dye-containing layer. The horizontal alignment film can be obtained by applying a composition containing a material having a horizontal alignment restricting force and a solvent (for example, the solvent exemplified in the dye-containing layer) to a substrate, removing the solvent, and then drying the coating film. From the viewpoint of quality, it is preferable to use a photo-aligning film as the horizontal alignment film.
[0249] Drying methods include natural drying, forced-air drying, heat drying, and reduced-pressure drying. Heat drying is preferred from a productivity standpoint, and in that case, the heating temperature is preferably such that the solvent can be removed and is above the phase transition temperature of the polymerizable liquid crystal compound. The procedures and conditions in such a process are examples of procedures and conditions that can be used in the production of the dye-containing layer.
[0250] The resulting dried coating film is irradiated with active energy rays (more specifically, ultraviolet light, etc.), and the polymerizable liquid crystal compound is polymerized while maintaining its orientation horizontally to the coating film plane, thereby forming a horizontally oriented liquid crystal layer. Examples of polymerization methods include those used in the production of dye-containing layers.
[0251] (Stretched film that constitutes the polarizing layer) The polarizing layer may be a stretched film on which a dye having absorption anisotropy is adsorbed. A polarizing layer composed of such a stretched film can usually be manufactured by a process of uniaxial stretching of a polyvinyl alcohol-based resin film, a process of dyeing the polyvinyl alcohol-based resin film with a dye having absorption anisotropy to adsorb the dye, a process of treating the polyvinyl alcohol-based resin film on which the dye having absorption anisotropy is adsorbed with an aqueous boric acid solution, and a process of washing with water after treatment with the aqueous boric acid solution. The polarizing layer may also be incorporated into an optical laminate as a polarizing plate in which a transparent protective film is laminated on one or both sides via an adhesive.
[0252] Polyvinyl alcohol-based resins are obtained by saponifying polyvinyl acetate-based resins. Polyvinyl acetate-based resins include polyvinyl acetate, which is a homopolymer of vinyl acetate, as well as copolymers of vinyl acetate with other monomers copolymerizable thereto. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and acrylamides having ammonium groups.
[0253] The degree of saponification of the polyvinyl alcohol-based resin is typically around 85 to 100 mol%, preferably 98 mol% or higher. The polyvinyl alcohol-based resin may be modified; for example, polyvinyl formal or polyvinyl acetal modified with aldehydes can also be used. The degree of polymerization of the polyvinyl alcohol-based resin is typically around 1,000 to 10,000, preferably in the range of 1,500 to 5,000.
[0254] A film made from such a polyvinyl alcohol-based resin is used as the base film for the polarizing layer. The method for producing the polyvinyl alcohol-based resin film is not particularly limited and can be done by known methods. The film thickness of the polyvinyl alcohol-based base film can be, for example, about 10 to 150 μm.
[0255] Uniaxial stretching of polyvinyl alcohol-based resin films can be performed before, simultaneously with, or after dyeing with an absorption-anisotropic dye. When uniaxial stretching is performed after dyeing, it may be performed before or during boric acid treatment. It is also possible to perform uniaxial stretching at multiple stages. Uniaxial stretching may be performed uniaxially between rolls with different peripheral speeds, or using a heated roll. Uniaxial stretching may be performed using dry stretching in the atmosphere, or wet stretching in which the polyvinyl alcohol-based resin film is swollen with a solvent before stretching. The stretching ratio is usually around 3 to 8 times.
[0256] Dyeing of polyvinyl alcohol-based resin films with absorption-anisotropic dyes is performed, for example, by immersing the polyvinyl alcohol-based resin film in an aqueous solution containing an absorption-anisotropic dye.
[0257] Specifically, iodine and dichroic organic dyes are used as dyes exhibiting absorption anisotropy. Examples of dichroic organic dyes include dichroic direct dyes made from disazo compounds such as CIDIRECT RED 39, and dichroic direct dyes made from compounds such as trisazo and tetrakissazo. It is preferable to immerse the polyvinyl alcohol-based resin film in water before dyeing.
[0258] When using iodine as a dye with anisotropic absorption, a dyeing method is typically employed in which a polyvinyl alcohol-based resin film is immersed in an aqueous solution containing iodine and potassium iodide. The iodine content in this aqueous solution is usually about 0.01 to 1 part by mass per 100 parts by mass of water. The potassium iodide content is usually about 0.5 to 20 parts by mass per 100 parts by mass of water. The temperature of the aqueous solution used for dyeing is usually about 20 to 40°C. The immersion time (dyeing time) in this aqueous solution is usually about 20 to 1,800 seconds.
[0259] On the other hand, when using dichroic organic dyes as absorption anisotropy dyes, a method of dyeing is usually employed in which a polyvinyl alcohol-based resin film is immersed in an aqueous solution containing a water-soluble dichroic dye. The content of the dichroic organic dye in this aqueous solution is usually 1 × 10⁻¹⁶ per 100 parts by mass of water. -4 It is approximately 10 parts by mass, preferably 1 × 10 -3 It is approximately 1 part by mass, and more preferably 1 × 10⁻⁶ -3 ~1 × 10 -2 This is in parts by mass. This aqueous solution may contain inorganic salts such as sodium sulfate as dyeing aids. The temperature of the aqueous solution containing the dichroic dye used for dyeing is usually around 20 to 80°C. The immersion time (dyeing time) in this aqueous solution is usually around 10 to 1,800 seconds.
[0260] The boric acid treatment after dyeing with an absorption-anisotropic dye can usually be carried out by immersing the dyed polyvinyl alcohol-based resin film in an aqueous boric acid solution. The boric acid content in this aqueous boric acid solution is usually about 2 to 15 parts by mass, preferably 5 to 12 parts by mass, per 100 parts by mass of water. When iodine is used as the absorption-anisotropic dye, it is preferable that this aqueous boric acid solution contains potassium iodide, in which case the potassium iodide content is usually about 0.1 to 15 parts by mass, preferably 5 to 12 parts by mass, per 100 parts by mass of water. The immersion time in the aqueous boric acid solution is usually about 60 to 1,200 seconds, preferably 150 to 600 seconds, and more preferably 200 to 400 seconds. The temperature of the boric acid treatment is usually 50°C or higher, preferably 50 to 85°C, and more preferably 60 to 80°C.
[0261] Polyvinyl alcohol-based resin films treated with boric acid are typically washed with water. This washing can be performed, for example, by immersing the boric acid-treated polyvinyl alcohol-based resin film in water. The water temperature during washing is usually around 5 to 40°C, and the immersion time is usually around 1 to 120 seconds.
[0262] After washing with water, the polarizing layer is dried to obtain the polarizing layer. The drying process can be carried out, for example, using a hot air dryer or a far-infrared heater. The drying temperature is usually around 30 to 100°C, preferably 50 to 80°C. The drying time is usually around 60 to 600 seconds, preferably 120 to 600 seconds. The drying process reduces the moisture content of the polarizing layer to a practical level. The moisture content is usually around 5 to 20% by weight, preferably 8 to 15% by weight. If the moisture content falls below 5% by weight, the flexibility of the polarizing layer is lost, and the polarizing layer may be damaged or fractured after drying. Also, if the moisture content exceeds 20% by weight, the thermal stability of the polarizing layer may deteriorate.
[0263] The thickness of the polarizing layer obtained by uniaxial stretching, dyeing with an absorption-anisotropic dye, boric acid treatment, water washing, and drying of the polyvinyl alcohol-based resin film is preferably 5 to 40 μm.
[0264] (A polarizing layer formed by coating a substrate film with a dye having absorption anisotropy.) Polarizing layers formed by coating a substrate film with an absorption-anisotropic dye include compositions containing liquid crystalline and absorption-anisotropic dyes, or compositions containing an absorption-anisotropic dye and a polymerizable liquid crystal, which are coated onto a substrate film. Examples of substrate films include those previously exemplified as substrates that can be used to manufacture the dye-containing layer.
[0265] The total thickness of the base film and polarizing layer formed as described above is preferably small, but if it is too small, the strength decreases and the processability tends to be poor. Therefore, it is usually 20 μm or less, preferably 5 μm or less, and more preferably 0.5 to 3 μm.
[0266] Specifically, the polarizing layer mentioned above is the polarizing layer described in Japanese Patent Publication No. 2013-33249, etc.
[0267] The polarizing layer obtained as described above (a stretched film, or a polarizing layer formed by coating a substrate film with an absorption-anisotropic dye) may be incorporated into an optical laminate in the form of a polarizing plate, with a transparent protective film laminated on one or both sides via an adhesive. The second protective film 152 and the second hard coat layer 162 constituting the transparent protective film can preferably be those previously exemplified as substrates that can be used to manufacture the dye-containing layer, and those exemplified as protective films and hard coat layers described later. In a polarizing layer formed by coating a substrate film with an absorption-anisotropic dye, the substrate film may be a transparent protective film.
[0268] (Hard court layer (first hard court layer)) A hard coat layer (first hard coat layer) can be provided on the side opposite to the polarizing layer of the dye-containing layer to protect the surface of the dye-containing layer. The hard coat layer is preferably a cured layer of any suitable UV-curable resin. Examples of UV-curable resins include acrylic resins, silicone resins, polyester resins, urethane resins, amide resins, epoxy resins, etc. The hard coat layer may contain any suitable additives as needed. Typical examples of such additives include inorganic fine particles and / or organic fine particles. By including fine particles, for example, an appropriate refractive index can be obtained.
[0269] The thickness of the hard coat layer can be set to any appropriate value. Preferably it is 50 μm or less, more preferably 1 to 50 μm, even more preferably 1 to 40 μm, and particularly preferably 1 to 30 μm. The pencil hardness of the hard coat layer is preferably 4H or higher, and even more preferably 5H to 8H.
[0270] The hard coat layer is typically provided in the optical laminate by applying a hard coat treatment to a substrate such as a protective film (first protective film) to form a laminate. The substrate can be a resin film as described later in the section on protective films, or a substrate used in the manufacturing method of the dye-containing layer described above.
[0271] The hard coat layer may be formed by applying the above-mentioned UV-curable resin to the surface of the pigment-containing layer or the surface of the protective film.
[0272] (Protective film (First protective film)) A protective film (first protective film) can be provided on the side of the dye-containing layer opposite the polarizing layer to protect the surface of the dye-containing layer. Any suitable film can be used as the protective film. Specific examples of materials that make up the main component of the film include cellulosic resins such as triacetylcellulose (TAC), polyester, polyvinyl alcohol, polycarbonate, polyamide, polyimide, polyethersulfone, polysulfone, polystyrene, polynorbornene, polyolefin, (meth)acrylic, acetate, and other transparent resins. Thermosetting resins or UV-curing resins such as (meth)acrylic, urethane, (meth)acrylic urethane, epoxy, and silicone can also be used. In addition, glassy polymers such as siloxane polymers can also be used. Furthermore, polymer films described in Japanese Patent Application Publication No. 2001-343529 (International Publication No. 2001 / 37007) can also be used. As materials for this film, for example, a resin composition containing a thermoplastic resin having substituted or unsubstituted imide groups in its side chains and a thermoplastic resin having substituted or unsubstituted phenyl groups and nitrile groups in its side chains can be used. Examples include a resin composition having an alternating copolymer of isobutene and N-methylmaleimide and an acrylonitrile-styrene copolymer. The polymer film may be, for example, an extruded product of the above resin composition. In this specification, (meth)acrylic means acrylic and / or methacrylic.
[0273] The above (meth)acrylic resin has a glass transition temperature (Tg) of preferably 115°C or higher, more preferably 120°C or higher, even more preferably 125°C or higher, and particularly preferably 130°C or higher. This is because it can have excellent durability. The upper limit of the Tg of the above (meth)acrylic resin is not particularly limited, but from the viewpoint of moldability and the like, it is preferably 170°C or lower.
[0274] As the (meth)acrylic resin mentioned above, any suitable (meth)acrylic resin can be used within a range that does not impair the effects of the present invention. Examples include poly(meth)acrylic acid esters such as polymethyl methacrylate, methyl methacrylate-(meth)acrylic acid copolymers, methyl methacrylate-(meth)acrylic acid ester copolymers, methyl methacrylate-acrylic acid ester-(meth)acrylic acid copolymers, methyl (meth)acrylic acid-styrene copolymers (MS resin, etc.), and polymers having alicyclic hydrocarbon groups (for example, methyl methacrylate-cyclohexyl methacrylate copolymer, methyl methacrylate-norbornyl (meth)acrylic acid copolymer, etc.). Preferably, poly(meth)acrylic acid C1-6 alkyl such as polymethyl (meth)acrylate is used. More preferably, a methyl methacrylate resin having methyl methacrylate as the main component (50-100% by weight, preferably 70-100% by weight) is used.
[0275] Specific examples of the above-mentioned (meth)acrylic resins include, for example, Acrypet VH and Acrypet VRL20A manufactured by Mitsubishi Rayon Co., Ltd., (meth)acrylic resins having a ring structure within the molecule as described in Japanese Patent Publication No. 2004-70296, and high Tg (meth)acrylic resins obtained by intramolecular crosslinking or intramolecular cyclization reactions.
[0276] As the above-mentioned (meth)acrylic resin, a (meth)acrylic resin having a lactone ring structure is particularly preferred in that it has high heat resistance, high transparency, and high mechanical strength.
[0277] Examples of (meth)acrylic resins having the above-mentioned lactone ring structure include those described in Japanese Patent Publication No. 2000-230016, Japanese Patent Publication No. 2001-151814, Japanese Patent Publication No. 2002-120326, Japanese Patent Publication No. 2002-254544, Japanese Patent Publication No. 2005-146084, and others.
[0278] The (meth)acrylic resin having the above-mentioned lactone ring structure has a mass-average molecular weight (sometimes referred to as weight-average molecular weight) of preferably 1,000 to 2,000,000, more preferably 5,000 to 1,000,000, even more preferably 1,000 to 500,000, and particularly preferably 50,000 to 500,000.
[0279] The (meth)acrylic resin having the above-mentioned lactone ring structure preferably has a Tg (glass transition temperature) of 115°C or higher, more preferably 125°C or higher, even more preferably 130°C or higher, particularly preferably 135°C, and most preferably 140°C or higher, from the viewpoint of durability. The upper limit of the Tg of the (meth)acrylic resin having the above-mentioned lactone ring structure is not particularly limited, but from the viewpoint of moldability and the like, it is preferably 170°C or lower.
[0280] The protective film is preferably transparent and colorless. The phase difference value Rth(590) in the thickness direction of the protective film at a wavelength of 590 nm is preferably -90 nm to +90 nm, more preferably -80 nm to +80 nm, and even more preferably -70 nm to +70 nm.
[0281] The surface of the protective film opposite to the polarizing layer may be treated with a hard coat, anti-reflective coating, anti-sticking coating, anti-glare coating, etc.
[0282] The thickness of the protective film can be any appropriate thickness, but is preferably 200 μm or less, more preferably 1 to 200 μm, even more preferably 3 to 150 μm, and particularly preferably 5 to 100 μm.
[0283] (Bonding layer) The bonding layer provided in the optical laminate can be a known adhesive layer or bonding agent layer.
[0284] The adhesive layer is a layer formed using an adhesive. In this specification, an adhesive is a substance that exhibits adhesive properties when it is attached to a substrate such as a panel, and is referred to as a pressure-sensitive adhesive. Any conventionally known adhesive with excellent optical transparency can be used without particular limitation, for example, an adhesive having a base polymer such as acrylic, urethane, silicone, or polyvinyl ether can be used. The thickness of the adhesive layer may be 3 μm or more, 5 μm or more, 35 μm or less, or 30 μm or less.
[0285] The adhesive layer may contain additives such as UV absorbers, antistatic agents using ionic compounds, solvents, crosslinking catalysts, tackifiers, plasticizers, softeners, dyes, pigments, and inorganic fillers.
[0286] The adhesive layer can be formed by curing the curable component in the adhesive. Examples of adhesives used to form the adhesive layer include adhesives other than pressure-sensitive adhesives (tacks), such as water-based adhesives and active energy ray curing adhesives like UV-curing adhesives. [Examples]
[0287] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Unless otherwise specified, "%" and "parts" in the examples and comparative examples refer to mass percent and parts by mass.
[0288] <Fabrication of horizontally aligned liquid crystal layer (phase difference layer)> (1) Preparation of composition for forming horizontally aligned film A composition for forming horizontally aligned films was obtained by mixing 5 parts of a photo-oriented material with the structure shown below (weight-average molecular weight: 30,000) and 95 parts of cyclopentanone (solvent) as components, and stirring the resulting mixture at 80°C for 1 hour. [ka]
[0289] (2) Preparation of polymerizable liquid crystal compounds Polymerizable liquid crystal compounds (X1) and (X2) having the molecular structures described below were prepared. Polymerizable liquid crystal compound (X1) was produced in accordance with the method described in Japanese Patent Publication No. 2010-31223. Polymerizable liquid crystal compound (X2) was produced in accordance with the method described in Japanese Patent Publication No. 2009-173893.
[0290] Polymerizable liquid crystal compound (X1): [ka]
[0291] Polymerizable liquid crystal compound (X2): [ka]
[0292] A solution was obtained by dissolving 1 mg of polymerizable liquid crystal compound (X1) in 50 mL of tetrahydrofuran. The obtained solution was placed in a measurement cell with a path length of 1 cm and used as the measurement sample. The measurement sample was set in a UV-Vis spectrophotometer (Shimadzu Corporation "UV-2450") and the absorption spectrum was measured. The wavelength at which the absorption maximum occurred was read from the obtained absorption spectrum, and the absorption maximum wavelength λmax in the wavelength range of 300-400 nm was found to be 350 nm.
[0293] (3) Preparation of polymerizable liquid crystal composition (A1) for forming a horizontally aligned liquid crystal layer Polymerizable liquid crystal compound (X1) and polymerizable liquid crystal compound (X2) were mixed in a mass ratio of 90:10 to obtain a mixture. To 100 parts of the obtained mixture, 0.1 parts of the leveling agent "BYK-361N" (manufactured by BM Chemie) and 6 parts of 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)butan-1-one ("Irgacure® 369 (Irg369)" manufactured by BASF Japan Ltd.) were added as photopolymerization initiators. Furthermore, N-methyl-2-pyrrolidone (NMP) was added to achieve a solid content concentration of 13%. By stirring this mixture at 80°C for 1 hour, a polymerizable liquid crystal composition (A1) for forming a horizontally aligned liquid crystal layer was obtained.
[0294] (4) Fabrication of horizontally aligned liquid crystal layer After corona treatment on a COP film (ZF-14-50) manufactured by Nippon Zeon Co., Ltd., the horizontal alignment film-forming composition obtained above was applied using a bar coater, dried at 80°C for 1 minute, and then subjected to integrated light intensity of 100 mJ / cm² at a wavelength of 313 nm using a polarized UV irradiation device (SPOT CURE SP-9; manufactured by Ushio Inc.). 2 A horizontally aligned film was obtained by polarized UV exposure. The thickness of the obtained horizontally aligned film was measured with an ellipsometer and found to be 200 nm.
[0295] Next, the polymerizable liquid crystal composition (A1) obtained above was applied to the horizontal alignment film using a bar coater, heated at 120°C for 60 seconds, and then ultraviolet light was irradiated from the surface coated with polymerizable liquid crystal composition (A1) using a high-pressure mercury lamp (UniCure VB-15201BY-A, manufactured by Ushio Inc.) (under a nitrogen atmosphere, integrated light intensity at a wavelength of 365 nm: 500 mJ / cm²). 2By doing so, a horizontally aligned liquid crystal layer was formed, and a laminated structure (A1) having a layer structure of COP film / horizontally aligned film / horizontally aligned liquid crystal layer was obtained. After confirming that there was no phase difference in the COP film, the in-plane phase difference values ReA(450) and ReA(550) of the laminated structure (A1) at wavelengths of 450 nm and 550 nm were measured using a KOBRA-WPR manufactured by Oji Instruments Co., Ltd., and ReA(550) was found to be 139 nm, and when ReA(450) / ReA(550) was calculated, it was 0.87.
[0296] <Preparation of the pigment-containing layer> (5) Preparation of polymerizable liquid crystal composition (C1) for forming a dye-containing layer As shown below, 100 parts of a polymerizable liquid crystal compound mixture obtained by mixing polymerizable liquid crystal compound (X3) and polymerizable liquid crystal compound (X4) in a mass ratio of 90:10 was mixed with 0.25 parts of the leveling agent "F-556" (manufactured by DIC Corporation), 0.9 parts of the dichroic dye A, and 6 parts of 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)butan-1-one ("Irgacure® 369 (Irg369)" manufactured by BASF Japan Ltd.) as a photopolymerization initiator. Furthermore, o-xylene was added to achieve a solid content concentration of 25%. By stirring this mixture at 80°C for 30 minutes, a polymerizable liquid crystal composition (C1) for forming a dye-containing layer was obtained.
[0297] Polymerizable liquid crystal compounds (X3) and (X4) were synthesized according to the method described in lub et al., Recl. Trav. Chim. Pays-Bas, 115, 321-328 (1996).
[0298] Polymerizable liquid crystal compound (X3): [ka]
[0299] Polymerizable liquid crystal compound (X4): [ka]
[0300] Dichroic dye A (maximum absorption wavelength 592 nm (measured in chloroform solution)): [ka]
[0301] (6) Preparation of dye-containing layer 1 A silane coupling agent "KBE-9103" (manufactured by Shin-Etsu Chemical Co., Ltd.) was dissolved in a mixed solvent of ethanol and water in a 9:1 (weight ratio) ratio to obtain a vertical alignment film-forming composition with a solid content of 1%. An HC-COP film 1 was prepared by forming a hard coat layer (HC layer) on a COP film (ZF-14-50) manufactured by Nippon Zeon Co., Ltd. After corona treatment of the hard coat layer side of this HC-COP film 1, the vertical alignment film-forming composition was applied using a bar coater and dried at 120°C for 1 minute to obtain a vertical alignment film. The thickness of the obtained vertical alignment film was measured with an ellipsometer and found to be 100 nm.
[0302] Next, the polymerizable liquid crystal composition (C1) was applied to the obtained vertical alignment film using a bar coater, dried at 120°C for 1 minute, and then irradiated with ultraviolet light from the side coated with the polymerizable liquid crystal composition (C1) using a high-pressure mercury lamp (UniCure VB-15201BY-A, manufactured by Ushio Inc.) (under a nitrogen atmosphere, integrated light intensity at a wavelength of 365 nm: 500 mJ / cm²). 2 By doing so, a dye-containing layer 1 was formed, and a laminated structure (D1) having a layer structure of COP film / hard coat layer / vertically aligned film / dye-containing layer 1 was obtained. The thickness of the dye-containing layer 1 was measured with an ellipsometer (M-220, JASCO Corporation) and was found to be 0.6 μm.
[0303] (7) Measurement of absorbance of the dye-containing layer 1 A sample for measurement was obtained by bonding the laminated structure (D1) obtained in (6) above to a piece of glass measuring 4 cm in length, 4 cm in width, and 0.7 mm in thickness via a 25 μm thick pressure-sensitive adhesive layer (manufactured by Lintec Corporation). The sample for measurement was prepared so that the dye-containing layer 1 side of the laminated structure (D1) was on the glass side. The sample for measurement was set in a UV-Vis spectrophotometer (Shimadzu Corporation "UV-2450") and the absorption maximum wavelength (λmax) in the range of 400 to 750 nm, and the absorbances AxC and AxC(z=60) in equations (1) and (2) above were determined. The absorbance AxC was measured after correcting the absorbance of the sample for measurement to zero at a wavelength of 800 nm. AxC(z=60) was also measured after setting the sample for measurement, tilting it, and correcting it so that the absorbance at a wavelength of 800 nm was zero. The absorption maximum wavelength (λmax) in the 400-750 nm range was 598 nm, AxC was 0.005, AxC(z=60) was 0.073, and AxC(z=60) / AxC was 14.6.
[0304] (8) Preparation of the dye-containing layer 2 Except for changing the bar coater and altering the coating thickness of the polymerizable liquid crystal composition (C1), the dye-containing layer 2 was prepared in the same manner as the dye-containing layer 1, and a laminated structure (D2) having a layer structure of COP film / hard coat layer / vertically aligned film / dye-containing layer 2 was obtained. The thickness of the dye-containing layer 2 was measured with an ellipsometer (M-220, JASCO Corporation) and was found to be 1.2 μm.
[0305] (9) Measurement of absorbance of dye-containing layer 2 The absorbance of dye-containing layer 2 was measured in the same manner as the absorbance measurement of dye-containing layer 1. The absorption maximum wavelength (λmax) in the wavelength range of 400-750 nm was 598 nm, AxC was 0.010, AxC(z=60) was 0.15, and AxC(z=60) / AxC was 15.0.
[0306] (10) Preparation of polymerizable liquid crystal composition (C2) for forming a dye-containing layer A polymerizable liquid crystal composition (C2) for forming a dye-containing layer was obtained in the same manner as the preparation of polymerizable liquid crystal composition (C1), except that the amount of dichroic dye A was changed to 1.8 parts per 100 parts of the polymerizable liquid crystal compound mixture.
[0307] (11) Preparation of the dye-containing layer 3 A dye-containing layer 3 was formed in the same manner as the dye-containing layer 1, except that polymerizable liquid crystal composition (C1) was changed to polymerizable liquid crystal composition (C2), and a laminated structure (D3) having a layer structure of COP film / hard coat layer / vertically aligned film / dye-containing layer 3 was obtained. The thickness of the dye-containing layer 3 was measured with an ellipsometer (M-220, JASCO Corporation) and was found to be 0.6 μm.
[0308] (12) Measurement of absorbance of the dye-containing layer 3 The absorbance of dye-containing layer 3 was measured in the same manner as the absorbance measurement of dye-containing layer 1. The absorption maximum wavelength (λmax) in the 400-750 nm range was 598 nm, AxC was 0.010, AxC(z=60) was 0.15, and AxC(z=60) / AxC was 15.0.
[0309] (13) Preparation of the dye-containing layer 4 Except for changing the bar coater and the coating thickness of the polymerizable liquid crystal composition (C2), the dye-containing layer 4 was prepared in the same manner as the dye-containing layer 3, and a laminated structure (D4) having a layer structure of COP film / hard coat layer / vertical alignment film / dye-containing layer 4 was obtained. The thickness of the dye-containing layer 4 was measured with an ellipsometer (M-220, JASCO Corporation) and was found to be 1.2 μm.
[0310] (14) Measurement of absorbance of the dye-containing layer 4 The absorbance of dye-containing layer 4 was measured in the same manner as the absorbance measurement of dye-containing layer 1. The absorption maximum wavelength (λmax) in the wavelength range of 400-750 nm was 598 nm, AxC was 0.010, AxC(z=60) was 0.28, and AxC(z=60) / AxC was 28.0.
[0311] (15) Preparation of water-based adhesives A water-based adhesive was prepared by dissolving 3 parts of carboxyl-modified polyvinyl alcohol (product name "KL-318" obtained from Kuraray Co., Ltd.) in 100 parts of water, and then adding 1.5 parts of a water-soluble epoxy resin, a polyamide epoxy additive (product name "Sumire's Resin (registered trademark) 650(30)" obtained from Taoka Chemical Industry Co., Ltd., an aqueous solution with a solid content concentration of 30%) to this aqueous solution.
[0312] (16) Preparation of UV-curable adhesive compositions After mixing the cationic curable components a1 to a3 and cationic polymerization initiators shown below, the cationic polymerization initiator and sensitizer shown below were further mixed, and the resulting mixture was degassed to prepare an ultraviolet-curable adhesive composition. The amounts shown below are based on the solid content. • Cationic curing component a1 (70 parts): 3',4'-Epoxycyclohexylmethyl 3',4'-Epoxycyclohexanecarboxylate (Product name: CEL2021P, manufactured by Daicel Corporation) • Cationic curing component a2 (20 parts): Neopentyl glycol diglycidyl ether (product name: EX-211, manufactured by Nagase ChemteX Corporation) • Cationic curing component a3 (10 parts): 2-Ethylhexylglycidyl ether (Trade name: EX-121, manufactured by Nagase ChemteX Corporation) • Cationic polymerization initiator (2.25 parts (solid content)): Product Name: 50% propylene carbonate solution of CPI-100 (manufactured by Sunapro Co., Ltd.) • Sensitizer (2 parts): 1,4-diethoxynaphthalene
[0313] <Fabrication of polarizing plates> (17) Fabrication of a polarizing layer A 20 μm thick polyvinyl alcohol-based resin film was stretched and stained with iodine to obtain a polarized layer (8 μm thick) in which iodine was adsorbed and oriented on the polyvinyl alcohol-based resin film. The total stretching ratio in this stretching process was 5.2 times.
[0314] (18) Fabrication of polarizing plates A hard-coated cyclic olefin resin film (HC-COP film 2) was prepared by forming a hard coat layer (HC layer) (3 μm thick) on one side of a cyclic polyolefin resin film (COP film) (13 μm thick). The pencil hardness of the HC layer side surface of this HC-COP film 2 was 5B. The COP film side (opposite side from the HC layer) of this HC-COP film 2 was bonded to one side of the polarizing layer obtained in (17) above via the water-based adhesive prepared in (15) above. The in-plane phase difference value Re(550) of this HC-COP film 2 at a wavelength of 550 nm was 0 nm, and the total light transmittance Ht(%) was measured in accordance with JIS K7105 using an integrating sphere type light transmittance measuring device (Haze Meter Hz-V3 manufactured by Suga Test Instruments Co., Ltd.), and it was 0.1%.
[0315] When the optical properties were confirmed using a spectrophotometer (V7100, manufactured by JASCO) with the polarization layer side of the polarizing plate as the incident surface, the luminous efficiency-corrected single-unit transmittance was 42.1%, the luminous efficiency-corrected polarization degree was 99.996%, the single-unit hue a was -1.1, and the single-unit hue b was 3.7.
[0316] <Fabrication of optical laminates (manufacturing intermediates)> [Example 1] (Fabrication of optical laminate (E1)) As a protective film with a hard coat layer, a hard-coated cyclic olefin resin film (thickness 16 μm) (hereinafter sometimes referred to as "16HC-COP film") was prepared, in which a hard coat layer (HC layer) (thickness 3 μm) was formed on one side of a cyclic polyolefin resin film (COP film) (thickness 13 μm). The pencil hardness of the HC layer side surface of this 16HC-COP film was 3B. A protective film was laminated to the hard coat layer side of this 16HC-COP film. The laminated structure (D1) obtained above was laminated to the COP film side (opposite side from the hard coat layer side) of the 16HC-COP film via the ultraviolet-curable adhesive composition (thickness 2 μm) prepared in (16) above, so that the dye-containing layer side was on the 16HC-COP film side. Subsequently, from the laminated structure (D1) side (COP film side), an ultraviolet irradiation device with a belt conveyor (using Fusion UV Systems' "H-bulb" lamp) irradiates the UVA region with an irradiation intensity of 390 W / cm². 2 The cumulative light intensity is 420 mJ / cm². 2 Therefore, in the UVB region, the radiation level is 400 mW / cm². 2 The cumulative light intensity is 400 mJ / cm². 2 To achieve this, ultraviolet light was irradiated to cure the ultraviolet-curable adhesive composition, forming an adhesive layer and obtaining a laminate. This laminate has a layer structure of protective film / hard coat layer (pencil hardness 3B) / COP film / adhesive layer (cured layer of ultraviolet-curable adhesive composition) / dye-containing layer 1 / vertical alignment film / hard coat layer / COP film. Subsequently, the COP film (ZF-14-50) of the obtained laminate was peeled off, and the HC-COP film 2 side of the polarizing plate obtained in (18) above was bonded to the exposed surface via an adhesive layer (Lintec Corporation, pressure-sensitive adhesive, 5 μm).
[0317] Next, the laminated structure (A1) obtained in (4) above was bonded to the polarizing layer side of the polarizing plate bonded to the above laminate via an adhesive layer (Lintec Corporation, pressure-sensitive adhesive, 5 μm) so that the horizontally aligned liquid crystal layer side was the polarizing plate side, and the COP film (ZF-14-50) was peeled off to obtain the optical laminate (E1). At this time, the bonding was performed so that the angle between the absorption axis of the polarizing layer and the slow axis of the horizontally aligned liquid crystal layer was 45°. The layer structure of the optical laminate (E1) is: protective film / hard coat layer (pencil hardness 3B) / COP film / adhesive layer (cured product layer of UV-curable adhesive composition) / dye-containing layer 1 / vertical alignment film / hard coat layer / adhesive layer / hard coat layer (pencil hardness 5B) / COP film / adhesive layer (cured product layer of water-based adhesive) / polarizing layer / adhesive layer / horizontally aligned liquid crystal layer (phase difference layer) / horizontal alignment film. The adhesive layer used in this optical laminate (E1) had a total light transmittance Ht (%) of 0.1% when measured using an integrating sphere type light transmittance measuring device (Haze Meter Hz-V3, manufactured by Suga Test Instruments Co., Ltd.) in accordance with JIS K7105.
[0318] [Example 2] (Fabrication of optical laminate (E2)) Optical laminate (E2) was fabricated in the same manner as optical laminate (E1), except that the laminated structure (D1) was changed to laminated structure (D2), the UV-curable adhesive composition was changed to an adhesive layer (Lintec Corporation, pressure-sensitive adhesive, 5 μm), and UV irradiation after bonding with laminated structure (D2) was not performed. The layer structure of optical laminate (E2) is: protective film / hard coat layer (pencil hardness 3B) / COP film / adhesive layer / dye-containing layer 2 / vertical alignment film / hard coat layer / adhesive layer / hard coat layer (pencil hardness 5B) / COP film / adhesive layer (cured layer of water-based adhesive) / polarizing layer / adhesive layer / horizontal alignment liquid crystal layer (phase difference layer) / horizontal alignment film. The adhesive layer used in this optical laminate (E2) all had a total light transmittance Ht (%) of 0.1% when measured using an integrating sphere type light transmittance measuring device (Haze Meter Hz-V3, manufactured by Suga Test Instruments Co., Ltd.) in accordance with JIS K7105.
[0319] [Examples 3-5] Optical laminates (E3) to (E5) were fabricated in the same manner as optical laminate (E1), except that the laminated structure (D1) was changed to laminated structures (D2) to (D4).
[0320] <Fabrication of vertically aligned liquid crystal layers> (19) Fabrication of vertically aligned liquid crystal layer 1 To 100 parts of Paliocolor LC242 (a registered trademark of BASF), a polymerizable liquid crystal compound, 0.1 parts of F-556 as a leveling agent and 3 parts of Irgacure 369 as a polymerization initiator were added. Cyclopentanone was added to achieve a solid content concentration of 13% to obtain a polymerizable liquid crystal composition (C3). Next, a vertically aligned liquid crystal layer 1 was formed on a vertically aligned film formed on a hard coat layer in the same manner as the preparation of the dye-containing layer 1 described in (6) above, except that the polymerizable liquid crystal composition (C3) was used, to obtain a laminated structure (D5).
[0321] (20) Measurement of the phase difference in the thickness direction of the vertically aligned liquid crystal layer 1 To confirm the orientation of the polymerizable liquid crystal compound in the vertically aligned liquid crystal layer 1, after confirming that there was no phase difference in the COP film, the phase difference value in the thickness direction of the laminated structure (D5) was measured as the phase difference value RthC in the thickness direction of the vertically aligned liquid crystal layer 1 using a KOBRA-WPR manufactured by Oji Instruments Co., Ltd. Since the above measuring instrument cannot measure the phase difference of films with anisotropic absorption of visible light, the RthC(λ) of a vertically aligned liquid crystal cured film excluding dichroic dyes was measured as a reference. During the measurement, the angle of incidence of light to the laminated structure (D5) was varied, and the front phase difference value of the vertically aligned liquid crystal layer 1 and the phase difference value when tilted 40° around the phase-advancing axis were measured. The average refractive index at each wavelength was measured using an ellipsometer M-220 manufactured by JASCO Corporation. The thickness of the vertically aligned liquid crystal layer 1 was measured using an Optical NanoGauge film thickness gauge C12562-01 manufactured by Hamamatsu Photonics K.K. From the front phase difference value measured above, the phase difference value when tilted 40° around the phase advance axis, the average refractive index, and the thickness of the vertically aligned liquid crystal layer 1, the three-dimensional refractive index was calculated with reference to the Oji Instruments Technical Data (http: / / www.oji-keisoku.co.jp / products / kobra / reference.html). From the obtained three-dimensional refractive index, the phase difference value RthC(λ) in the thickness direction of the vertically aligned liquid crystal layer 1 was calculated according to equation (7) above. As a result, RthC(550) was -70 nm, and RthC(450) / RthC(550) was 1.10.
[0322] (21) Fabrication of vertically aligned liquid crystal layer 2 A vertically aligned liquid crystal layer 2 was formed in the same manner as the vertically aligned liquid crystal layer 1, except that the bar coater was changed and the coating thickness of the polymerizable liquid crystal composition (C3) was changed, thereby obtaining a laminated structure (D6).
[0323] (22) Measurement of the phase difference in the thickness direction of the vertically aligned liquid crystal layer 2 The phase difference value RthC(λ) in the thickness direction of vertically aligned liquid crystal layer 2 was calculated in the same manner as the phase difference in the thickness direction of vertically aligned liquid crystal layer 1. As a result, RthC(550) was -140 nm, and RthC(450) / RthC(550) was 1.10.
[0324] <Fabrication of optical stacks> [Example 6] (Fabrication of optical laminate (F1)) In Example 1, the laminated structure (D5) prepared in (19) was bonded to the horizontal alignment film side of the laminated structure (A1) of the optical laminate (E1) via an adhesive layer (2 μm thick) formed using the UV-curable adhesive prepared in (16) above, with the vertical alignment liquid crystal layer 1 side facing the optical laminate (E1). Subsequently, from the laminated structure (D5) side (COP film side), UV irradiation was performed using a belt conveyor-equipped UV irradiation device (using a "H bulb" lamp manufactured by Fusion UV Systems) at an irradiation intensity of 390 W / cm² in the UVA range. 2 The cumulative light intensity is 420 mJ / cm². 2 Therefore, in the UVB region, the radiation level is 400 mW / cm². 2 The cumulative light intensity is 400 mJ / cm². 2 To achieve this, ultraviolet light was irradiated to cure the ultraviolet-curable adhesive composition, forming an adhesive layer, and the COP film (ZF-14-50) was peeled off to obtain an optical laminate (F1). The layer structure of the optical laminate (F1) is: protective film / hard coat layer (pencil hardness 3B) / COP film / adhesive layer (cured layer of ultraviolet-curable adhesive composition) / dye-containing layer 1 / vertical alignment film / hard coat layer / adhesive layer / hard coat layer (pencil hardness 5B) / COP film / adhesive layer (cured layer of water-based adhesive) / polarizing layer / adhesive layer / horizontal alignment liquid crystal layer (phase difference layer) / horizontal alignment film / adhesive layer (cured layer of ultraviolet-curable adhesive composition) / vertical alignment liquid crystal layer 1 / vertical alignment film / hard coat layer.
[0325] (Fabrication of optical laminate with adhesive layer (G1)) An adhesive layer (Lintec Corporation, pressure-sensitive adhesive, 25 μm) was bonded to the vertically aligned liquid crystal layer side of the laminated structure (D5) of the optical laminate (F1) to obtain an optical laminate with an adhesive layer (G1). The layer structure of the optical laminate with an adhesive layer (G1) is: protective film / hard coat layer (pencil hardness 3B) / COP film / adhesive layer (cured layer of UV-curable adhesive composition) / dye-containing layer 1 / vertical alignment film / hard coat layer / adhesive layer / hard coat layer (pencil hardness 5B) / COP film / adhesive layer (cured layer of water-based adhesive) / polarizing layer / adhesive layer / horizontally aligned liquid crystal layer (phase difference layer) / horizontally aligned film / adhesive layer (cured layer of UV-curable adhesive composition) / vertical alignment liquid crystal layer 1 / vertical alignment film / hard coat layer / adhesive layer.
[0326] [Examples 7-9] Optical laminates (F2) to (F4) and optical laminates with adhesive layers (G2) to (G4) were fabricated in the same manner as the optical laminates (F1) and optical laminates with adhesive layers (G1), except that optical laminate (E1) was changed to the optical laminate shown in Table 1 (optical laminates obtained in Examples 3 to 5).
[0327] [Example 10] The optical laminate (F5) and the optical laminate with adhesive layer (G5) were fabricated in the same manner as the optical laminate (F2) and the optical laminate with adhesive layer (G2), except that the laminated structure (D5) used to stack the vertically aligned liquid crystal layers was changed to the laminated structure (D6) fabricated in (21) above.
[0328] [Example 11] Optical laminate (F6) and optical laminate with adhesive layer (G6) were fabricated in the same manner as the optical laminate (F2) and optical laminate with adhesive layer (G2), except that optical laminate (E1) was changed to optical laminate (E2) obtained in Example 2.
[0329] [Comparative Example 1] (Fabrication of optical laminate (F7)) A protective film was laminated to the hard coat layer side of the 16HC-COP film of the polarizing plate prepared in (18) above. The laminated structure (A1) obtained in (4) above was laminated to the polarizing layer side via an adhesive layer (Lintec Corporation, pressure-sensitive adhesive, 5 μm) so that the horizontally aligned liquid crystal layer side was on the polarizing plate side. The COP film (ZF-14-50) was peeled off to obtain an optical laminate (E6). The layer structure of the optical laminate (E6) is: protective film / hard coat layer (pencil hardness 5B) / COP film / adhesive layer (cured layer of water-based adhesive) / polarizing layer / adhesive layer / horizontally aligned liquid crystal layer (phase difference layer) / horizontal alignment film. The adhesive layer used in this optical laminate (E6) had a total light transmittance Ht (%) of 0.1% when measured using an integrating sphere type light transmittance measuring device (Haze Meter Hz-V3, manufactured by Suga Test Instruments Co., Ltd.) in accordance with JIS K7105.
[0330] The laminated structure (D1) prepared in (6) above was bonded to the horizontal alignment film side of the laminated structure (A1) of the optical laminate (E6) obtained above, via an adhesive layer (Lintec Corporation, pressure-sensitive adhesive, 5 μm), with the dye-containing layer 1 side facing the optical laminate (E1), and the COP film was peeled off to obtain the optical laminate (F7). The layer structure of the optical laminate (F7) is: protective film / hard coat layer (pencil hardness 5B) / COP film / adhesive layer (cured layer of water-based adhesive) / polarizing layer / adhesive layer / horizontally aligned liquid crystal layer (phase difference layer) / horizontally aligned film / adhesive layer / dye-containing layer 1 / vertical alignment film / hard coat layer.
[0331] The phase difference value RthC(λ) in the thickness direction of the dye-containing layer 1 was calculated in the same manner as the phase difference measurement in the thickness direction of the vertically aligned liquid crystal layer 1. As a result, RthC(550) was -70 nm, and RthC(450) / RthC(550) was 1.10.
[0332] (Fabrication of optical laminates with adhesive layer (G7)) An adhesive layer (Lintec Corporation, pressure-sensitive adhesive, 25 μm) was bonded to the vertically aligned liquid crystal layer side of the laminated structure (D1) of the optical laminate (F7) to obtain an optical laminate with an adhesive layer (G7). The layer structure of the optical laminate with an adhesive layer (G7) is: protective film / hard coat layer (pencil hardness 5B) / COP film / adhesive layer (cured layer of water-based adhesive) / polarizing layer / adhesive layer / horizontally aligned liquid crystal layer (phase difference layer) / horizontally aligned film / adhesive layer / dye-containing layer 1 / vertical alignment film / hard coat layer / adhesive layer.
[0333] [Comparative Example 2] The optical laminate (F8) and the optical laminate with adhesive layer (G8) were fabricated in the same manner as the optical laminate (F7) and the optical laminate with adhesive layer (G7), except that the laminated structure (D1) was changed to the laminated structure (D2) fabricated in (8) above.
[0334] The phase difference value RthC(λ) in the thickness direction of the dye-containing layer 2 was calculated in the same manner as the phase difference measurement in the thickness direction of the vertically aligned liquid crystal layer 1. As a result, RthC(550) was -140 nm, and RthC(450) / RthC(550) was 1.10.
[0335] [Comparative Example 3] The optical laminate (F9) and the optical laminate with adhesive layer (G9) were fabricated in the same manner as the optical laminate (F7) and the optical laminate with adhesive layer (G7), except that the laminated structure (D1) was changed to the laminated structure (D5) fabricated in (19) above.
[0336] <Rating> (Evaluation of early optical laminates with adhesive layers) The front glass and polarizing film were removed from a Samsung Galaxy S5 to extract the display device. The adhesive layer side of the optical laminate with adhesive, prepared using the method described above, was bonded, and the protective film was peeled off. Then, with the display device powered off (black display), the reflected hue was checked when viewed from the front and at an angle, and evaluated according to the evaluation criteria shown below. The results are shown in Tables 1 and 2. [Evaluation Criteria] A: I can't perceive any color. B: I can sense a slight color. C: I can sense the color. D: More colored
[0337] Next, using the same sample, the display device was powered on with maximum brightness, and all settings that change the screen display color, such as the blue light cut function and color balance adjustment, were turned off. With a white screen displayed (when displaying white) (with the HTML color code #FFFFFF displayed), the hue was checked when viewed from the front and at an angle, and evaluated according to the evaluation criteria described above.
[0338] (Evaluation of optical laminates with adhesive layer after heat resistance testing) The optical laminates with adhesive layers prepared using the method described above were placed in an oven set to 80°C and held for 240 hours to conduct a heat resistance test. The optical laminates with adhesive layers after the heat resistance test were evaluated using the same procedure as the evaluation of the initial optical laminates with adhesive layers. The results are shown in Tables 1 and 2.
[0339] [Table 1]
[0340] [Table 2] [Explanation of Symbols]
[0341] 1 Optical laminate, 5-7 Optical laminate, 11 Dye-containing layer, 12 Polarizing layer, 13 Phase difference layer, 15 Protective film (first protective film), 16 Hard coat layer (first hard coat layer), 17 Vertically aligned liquid crystal layer, 20 First laminate, 152 First protective film, 162 Second hard coat layer.
Claims
1. An optical laminate including, in this order, a dye-containing layer, a polarizing layer, and a retardation layer having an in-plane retardation, The dye-containing layer is Contains a dichroic dye having a maximum absorption in the wavelength range of 400 nm or more and 750 nm or less, An optical laminate satisfying the following formula (1) and the following formula (2). 0.001≦A×C≦0.3 (1) AxC (z=60) / AxC>2 (2) [In formula (1) and formula (2), AxC represents the absorbance of the dye-containing layer at a maximum absorption wavelength in the wavelength range of 400 nm or more and 750 nm or less, and represents the absorbance of linearly polarized light vibrating in the x-axis direction, AxC(z=60) is the absorbance of the dye-containing layer at a maximum absorption wavelength in the wavelength range of 400 nm or more and 750 nm or less, and represents the absorbance of linearly polarized light oscillating in the x-axis direction when the dye-containing layer is rotated 60° about the y-axis as the rotation axis, The x-axis represents an arbitrary direction in the plane of the dye-containing layer, and the y-axis represents a direction perpendicular to the x-axis in the plane of the dye-containing layer.
2. 2. The optical laminate according to claim 1, which is a manufacturing intermediate of a laminate including, in this order, the dye-containing layer, the polarizing layer, the retardation layer, and a vertically aligned liquid crystal layer cured in a state in which a polymerizable liquid crystal compound is aligned in the lamination direction of the optical laminate.
3. An optical laminate including, in this order, a dye-containing layer, a polarizing layer, a retardation layer having an in-plane retardation, and a vertically aligned liquid crystal layer, the vertically aligned liquid crystal layer is a cured layer obtained by curing a polymerizable liquid crystal compound in a state where the polymerizable liquid crystal compound is aligned in the lamination direction of the optical laminate, The dye-containing layer is Contains a dichroic dye having a maximum absorption in the wavelength range of 400 nm or more and 750 nm or less, An optical laminate satisfying the following formula (1) and the following formula (2). 0.001≦A×C≦0.3 (1) AxC (z=60) / AxC>2 (2) [In formula (1) and formula (2), AxC represents the absorbance of the dye-containing layer at a maximum absorption wavelength in the wavelength range of 400 nm or more and 750 nm or less, and represents the absorbance of linearly polarized light vibrating in the x-axis direction, AxC(z=60) is the absorbance of the dye-containing layer at a maximum absorption wavelength in the wavelength range of 400 nm or more and 750 nm or less, and represents the absorbance of linearly polarized light oscillating in the x-axis direction when the dye-containing layer is rotated 60° about the y-axis as the rotation axis, The x-axis represents an arbitrary direction in the plane of the dye-containing layer, and the y-axis represents a direction perpendicular to the x-axis in the plane of the dye-containing layer.
4. Further, an adhesive layer is provided between the retardation layer and the vertically aligned liquid crystal layer, The optical laminate according to claim 2 , wherein the adhesive layer is in direct contact with the retardation layer and the vertically aligned liquid crystal layer.
5. The optical laminate described in claim 4, wherein the adhesive layer is a cured layer of an ultraviolet-curable adhesive composition.
6. The optical laminate according to any one of claims 1 to 5, wherein the dye-containing layer further comprises a cured product in which a polymerizable liquid crystal compound is cured in a state where the polymerizable liquid crystal compound is aligned in the lamination direction of the optical laminate.
7. The retardation layer is a horizontally aligned liquid crystal layer in which a polymerizable liquid crystal compound is aligned in a direction perpendicular to the lamination direction of the optical laminate and cured. The optical laminate according to any one of claims 1 to 6.
8. The optical laminate according to any one of claims 1 to 7, wherein the retardation layer satisfies the following formula (3): ReA(450) / ReA(550)<1.00 (3) (In formula (3), ReA(450) and ReA(550) represent the in-plane retardation values of the retardation layer at wavelengths of 450 nm and 550 nm, respectively.)
9. The optical laminate according to any one of claims 1 to 8, wherein the retardation layer satisfies the following formula (4). 120 nm≦ReA(550)≦170 nm (4) [In formula (4), ReA(550) represents an in-plane retardation value of the retardation layer at a wavelength of 550 nm.]
10. 10. The optical laminate according to claim 1, wherein an angle between an absorption axis of the polarizing layer and a slow axis of the retardation layer is within a range of 45°±5°.
11. The optical laminate according to any one of claims 1 to 10, wherein the dichroic dye is an azo dye.
12. The optical laminate according to any one of claims 1 to 11, wherein the dye-containing layer satisfies any one of the following [a1] to [a3]. [a1] Having maximum absorption in both the wavelength range of 400 nm or more and less than 550 nm and the wavelength range of 550 nm or more and less than 7000 nm; [a2] has a maximum absorption in the wavelength range of 400 nm or more and less than 550 nm, and does not have a maximum absorption in the wavelength range of 550 nm or more and 700 nm or less; [a3] The compound has no maximum absorption in the wavelength range of 400 nm or more and less than 550 nm, and has a maximum absorption in the wavelength range of 550 nm or more and 700 nm or less.
13. The optical laminate according to any one of claims 1 to 12, further comprising a hard coat layer on the side of the dye-containing layer opposite to the polarizing layer.
14. The optical laminate according to any one of claims 1 to 13, further comprising a protective film on the side of the dye-containing layer opposite to the polarizing layer.
15. The optical laminate according to any one of claims 1 to 14 is provided, The display device, wherein the optical laminate is disposed such that the dye-containing layer is on a viewing side relative to the polarizing layer.
16. The display device according to claim 15, which is an organic electroluminescence display device.